Quantum dots and their applications

By adopting a ligand layer with a specific chemical formula structure on the surface of the quantum dot and improving its oxidation stability through the ligand exchange method, the problem of reducing the luminescence efficiency caused by oxidation of the quantum dot on the surface is solved, and excellent dispersion and luminescence performance are achieved.

CN111320978BActive Publication Date: 2025-03-07DONGWOO FINE CHEM CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN201911282576.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-02-22
Filing Date
2019-12-13
Publication Date
2025-03-07
Estimated Expiration
2039-12-13

AI Technical Summary

Technical Problem

The surface oxidation of existing quantum dots can easily lead to a decrease in luminescence efficiency, and when dispersing or forming specific functional groups in various solvents, the surface damage problem is difficult to solve.

Method used

The quantum dots of the ligand layer having a specific chemical formula structure on the surface are used to replace organic ligands such as oleic acid with compounds represented by formula 1 to 4 through ligand exchange methods to improve oxidation stability and dispersion.

Benefits of technology

The oxidation stability and reliability of quantum dots are improved, the reduction of luminescence efficiency is prevented, and excellent dispersion characteristics are shown in various solvents.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN111320978B_ABST
    Figure CN111320978B_ABST
Patent Text Reader

Abstract

The present invention provides quantum dots and their applications. The quantum dots of the present invention have a ligand layer on the surface, and the ligand layer contains one or more of the compounds represented by chemical formulas 1 to 4. The quantum dots of the present invention have excellent oxidation stability and can be effectively applied to quantum dot dispersions, quantum dot light conversion compositions, etc. In chemical formula 1, L is C 1 ‑C 22 alkylene, R is hydrogen or methyl, and n is an integer from 1 to 3; in Chemical Formula 2, R 1 For hydrogen, R 2 is an alkylene group having 1 to 30 carbon atoms; in chemical formula 3, R 3 is hydrogen or methyl, R 4 is a straight chain or branched chain alkylene group having 1 to 30 carbon atoms, and m is an integer of 1 to 100; in Chemical Formula 4, R 5 is hydrogen or methyl, R 6 is a straight-chain alkylene group having 1 to 30 carbon atoms, A is -O-, -NH-, etc., R 7 is an alkyl group having 1 to 10 carbon atoms, and l is an integer of 1 to 250.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to quantum dots, quantum dot dispersions, quantum dot light conversion compositions, self-luminous photosensitive resin compositions, quantum dot light emitting diodes, quantum dot films, color filters, light conversion laminated substrates and image display devices. Background Art

[0002] Quantum dots have high luminescence and a narrow luminescence spectrum. The luminescence wavelength can be adjusted by an excitation wavelength. They have the inherent property of being stable with respect to light. Therefore, a lot of research has been conducted so far on their use in important application fields such as biological imaging or energy conversion, and lighting (LED).

[0003] Such quantum dots are extremely sensitive to surface conditions and will oxidize from the surface due to the dispersed solvent or the surrounding environment, resulting in a sharp decrease in luminous efficiency. In order to achieve a variety of applications of quantum dots, in addition to the organic solvent in which they are initially dispersed, it is necessary to disperse them in a variety of solvents or form specific functional groups on the surface, but such a process will cause the surface of the quantum dots to be damaged, resulting in a problem of reduced luminous efficiency.

[0004] In order to overcome such problems, a large number of attempts have been made, and various methods have been proposed. One of them is the functional group replacement (ligand exchange) method of replacing the organic substance existing on the surface of quantum dots with molecules having desired functional groups. This method is a method of replacing the organic molecules existing on the surface of quantum dots with organic molecules suitable for the desired application location, but because it will directly affect the surface of quantum dots, it has the disadvantage of causing fatal problems to the luminous efficiency.

[0005] Korean Patent Publication No. 10-2018-0002716 and Korean Registered Patent No. 10-1628065 disclose quantum dots including ligands configured on the surface, but the actual situation is that due to low compatibility, the dispersibility is reduced, the stability and reliability are reduced, and therefore the problem of decreased light resistance over time cannot be solved.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Korean Patent Publication No. 10-2018-0002716

[0009] Patent Document 2: Korean Registered Patent No. 10-1628065 Summary of the invention

[0010] Issues to be solved

[0011] An object of the present invention is to provide quantum dots having excellent oxidation stability and reliability.

[0012] In addition, the present invention aims to provide a quantum dot film, a light conversion resin composition and a quantum dot light-emitting diode (QLED) comprising the above-mentioned quantum dots.

[0013] Another object of the present invention is to provide a color filter formed using the light conversion resin composition, a light conversion laminated substrate, and an image display device including the color filter or the light conversion laminated substrate.

[0014] Solution to the problem

[0015] The present invention provides a quantum dot having a ligand layer on the surface.

[0016] The ligand layer includes one or more compounds represented by the following Chemical Formula 1 to Chemical Formula 4.

[0017] [Chemical formula 1]

[0018]

[0019] In the above chemical formula 1,

[0020] L is C1-C 22 Alkylene or C4-C 22 The alkenylene

[0021] R is hydrogen or methyl,

[0022] n is an integer of 1 to 3.

[0023] [Chemical formula 2]

[0024]

[0025] In the above chemical formula 2,

[0026] R1 is hydrogen or methyl,

[0027] R2 is a straight chain or branched chain alkylene group having 1 to 30 carbon atoms, a straight chain or branched chain heteroalkylene group having 1 to 30 carbon atoms, a straight chain or branched chain alkenylene group having 2 to 30 carbon atoms, a cycloalkylene group having 3 to 30 carbon atoms, a heterocycloalkylene group having 3 to 30 carbon atoms, an alkyleneoxy group having 1 to 30 carbon atoms, an alkylene ester group having 1 to 30 carbon atoms, an arylene group having 6 to 20 carbon atoms, an arylalkylene group having 6 to 30 carbon atoms, or a heteroarylene group having 4 to 20 carbon atoms.

[0028] [Chemical formula 3]

[0029]

[0030] In the above chemical formula 3, R3 is hydrogen or methyl,

[0031] R4 is a linear or branched alkylene group having 1 to 30 carbon atoms, a linear or branched alkenylene group having 2 to 30 carbon atoms, a cycloalkylene group having 3 to 30 carbon atoms, a heterocycloalkylene group having 3 to 30 carbon atoms, an alkyleneoxy group having 1 to 30 carbon atoms, an alkyleneester group having 1 to 30 carbon atoms, an arylene group having 6 to 20 carbon atoms, an arylalkylene group having 6 to 30 carbon atoms, or a heteroarylene group having 4 to 20 carbon atoms,

[0032] m is an integer from 1 to 100.

[0033] [Chemical formula 4]

[0034]

[0035] In the above chemical formula 4,

[0036] R5 is hydrogen or methyl,

[0037] R6 is a linear or branched alkylene group having 1 to 30 carbon atoms, or an alkylene group containing an ester or an amide,

[0038] A is -O-, -NH- or -NR7-,

[0039] R7 is an alkyl group having 1 to 10 carbon atoms,

[0040] l is an integer from 1 to 250.

[0041] In addition, the present invention provides a quantum dot dispersion, a quantum dot light-emitting diode and a quantum dot film comprising the above quantum dots, and a quantum dot light conversion composition and a self-luminous photosensitive resin composition comprising the above quantum dot dispersion.

[0042] In addition, the present invention provides a color filter formed using the self-luminous photosensitive resin composition, and a light conversion laminate substrate formed using the quantum dot light conversion composition.

[0043] Furthermore, the present invention provides an image display device including the color filter or the light conversion layered substrate.

[0044] Effects of the Invention

[0045] The quantum dots of the present invention contain one or more compounds represented by specific chemical formula structures as ligand layers, thereby protecting the surface of the quantum dots and providing excellent oxidation stability and preventing the reduction of quantum efficiency. As a result, the quantum dots can provide the effect of improving brightness and reliability, and can be effectively applied to a variety of uses such as quantum dot films, quantum dot light-emitting diodes, color filters, and light conversion laminated substrates.

[0046] Furthermore, the quantum dot dispersion of the present invention not only has excellent viscosity stability but also has a good dispersed particle size and can exhibit excellent dispersion characteristics.

[0047] Furthermore, the quantum dot light conversion composition of the present invention is excellent in light conversion efficiency and coating hardness, and can also exhibit excellent characteristics in a continuous process.

[0048] In addition, the self-luminous photosensitive resin composition of the present invention has an excellent development speed when manufacturing a color filter, has little peeling of a fine pattern, can show excellent sensitivity, and can also provide excellent effects in terms of pattern stability. In addition, the color filter manufactured from the self-luminous photosensitive resin composition of the present invention can show high resolution due to the ability to realize a fine pattern, can show a relatively high light conversion efficiency and provide excellent brightness. DETAILED DESCRIPTION

[0049] Hereinafter, the present invention will be described in detail.

[0050] The present invention provides a quantum dot, characterized in that it has a ligand layer on the surface, and the ligand layer contains one or more of the compounds represented by the following chemical formulas 1 to 4:

[0051] [Chemical formula 1]

[0052]

[0053] In the above chemical formula 1,

[0054] L is C1-C 22 Alkylene or C4-C 22 The alkenylene

[0055] R is hydrogen or methyl,

[0056] n is an integer of 1 to 3.

[0057] [Chemical formula 2]

[0058]

[0059] In the above chemical formula 2,

[0060] R1 is hydrogen or methyl,

[0061] R2 is a straight chain or branched chain alkylene group having 1 to 30 carbon atoms, a straight chain or branched chain heteroalkylene group having 1 to 30 carbon atoms, a straight chain or branched chain alkenylene group having 2 to 30 carbon atoms, a cycloalkylene group having 3 to 30 carbon atoms, a heterocycloalkylene group having 3 to 30 carbon atoms, an alkyleneoxy group having 1 to 30 carbon atoms, an alkylene ester group having 1 to 30 carbon atoms, an arylene group having 6 to 20 carbon atoms, an arylalkylene group having 6 to 30 carbon atoms, or a heteroarylene group having 4 to 20 carbon atoms.

[0062] [Chemical formula 3]

[0063]

[0064] In the above chemical formula 3, R3 is hydrogen or methyl,

[0065] R4 is a linear or branched alkylene group having 1 to 30 carbon atoms, a linear or branched alkenylene group having 2 to 30 carbon atoms, a cycloalkylene group having 3 to 30 carbon atoms, a heterocycloalkylene group having 3 to 30 carbon atoms, an alkyleneoxy group having 1 to 30 carbon atoms, an alkyleneester group having 1 to 30 carbon atoms, an arylene group having 6 to 20 carbon atoms, an arylalkylene group having 6 to 30 carbon atoms, or a heteroarylene group having 4 to 20 carbon atoms,

[0066] m is an integer from 1 to 100.

[0067] [Chemical formula 4]

[0068]

[0069] In the above chemical formula 4,

[0070] R5 is hydrogen or methyl,

[0071] R6 is a linear or branched alkylene group having 1 to 30 carbon atoms, or an alkylene group containing an ester or an amide,

[0072] A is -O-, -NH- or -NR7-,

[0073] R7 is an alkyl group having 1 to 10 carbon atoms,

[0074] l is an integer from 1 to 250.

[0075] Furthermore, the present invention provides a quantum dot dispersion obtained by adding the above quantum dots to one or more of a monomer and a solvent and dispersing the mixture.

[0076] In addition, the present invention provides a quantum dot light-emitting diode (QLED) and a quantum dot film comprising the quantum dots.

[0077] In addition, the present invention provides a quantum dot light conversion composition or a self-luminous photosensitive resin composition comprising the above quantum dot dispersion.

[0078] In addition, the present invention provides a color filter formed using the self-luminous photosensitive resin composition, a light conversion layered substrate formed using the quantum dot light conversion composition, and an image display device including the color filter and / or the light conversion layered substrate.

[0079] The alkylene group used in the present specification means a linear or branched divalent hydrocarbon group, and includes, for example, a methylene group, an ethylene group, a n-propylene group, an isopropylene group, etc., but is not limited thereto.

[0080] The alkenylene group used in this specification means a straight-chain or branched divalent unsaturated hydrocarbon group having one or more carbon-carbon double bonds, including, for example, butenylene, pentenylene, hexenylene, heptenylene, octenylene, nonenylene, decenylene, undecenylene, dodecenylene, tridecenylene, tetradecenylene, pentadecenylene, heptadecenylene, octadecenylene, etc., but is not limited thereto.

[0081] In the present specification, "heteroalkylene", "heterocycloalkylene", "heteroarylalkylene" or "heteroarylene" means an alkylene, cycloalkylene, arylalkylene or arylene group containing one or more heteroatoms other than carbon atoms in the atoms constituting the chain or ring. The heteroatom may be one or more selected from oxygen (O), sulfur (S) and nitrogen (N), preferably oxygen (O).

[0082] <Quantum dot>

[0083] In the present invention, quantum dots are substances that can emit light by themselves through a light source and are used to emit light in the visible and infrared regions. Quantum dots are substances with a crystalline structure of several nanometers in size and can be composed of hundreds to thousands of atoms. Atoms form molecules, and molecules form a collection of small molecules called molecular clusters to form nanoparticles. Usually, such nanoparticles are called quantum dots, especially when they have semiconductor properties. The quantum dots of the present invention are not particularly limited as long as they meet such a concept. When an object is as small as a nanometer or less, the band gap of the object will show a phenomenon of enlargement, namely the quantum confinement effect. If the quantum dot obtains energy from the outside and reaches an excited state, it will spontaneously release energy corresponding to the band gap and emit light by itself.

[0084] The quantum dot of the present invention is characterized in that it has a ligand layer on the surface, and the ligand layer contains one or more compounds represented by the following chemical formulas 1 to 4. This can protect the surface of the quantum dot, improve oxidation stability, prevent the reduction of quantum efficiency, and improve reliability.

[0085] [Chemical formula 1]

[0086]

[0087] In the above chemical formula 1, L can be C1-C 22 Alkylene or C4-C 22 In addition, in the above chemical formula 1, R may be hydrogen or methyl, and n may be an integer of 1 to 3. Preferably, L is C1-C 11 The alkylene group is a alkylene group, R is hydrogen or methyl, and n is an integer of 1 to 3.

[0088] In one embodiment of the present invention, the compound represented by the above Chemical Formula 1 may be a compound represented by any one of the following Chemical Formulas 1-1 to 1-7.

[0089] [Chemical formula 1-1]

[0090]

[0091] [Chemical formula 1-2]

[0092]

[0093] [Chemical formula 1-3]

[0094]

[0095] [Chemical formula 1-4]

[0096]

[0097] [Chemical formula 1-5]

[0098]

[0099] [Chemical formula 1-6]

[0100]

[0101] [Chemical formula 1-7]

[0102]

[0103] [Chemical formula 2]

[0104]

[0105] In the above chemical formula 2, R1 can be hydrogen or methyl, and R2 can be a straight chain or branched chain alkylene group having 1 to 30 carbon atoms, a straight chain or branched chain heteroalkylene group having 1 to 30 carbon atoms, a straight chain or branched chain alkenylene group having 2 to 30 carbon atoms, a cycloalkylene group having 3 to 30 carbon atoms, a heterocycloalkylene group having 3 to 30 carbon atoms, an alkyleneoxy group having 1 to 30 carbon atoms, an alkylene ester group having 1 to 30 carbon atoms, an arylene group having 6 to 20 carbon atoms, an arylalkylene group having 6 to 30 carbon atoms, or a heteroarylene group having 4 to 20 carbon atoms.

[0106] Preferably, the above R2 can be a straight chain or branched alkylene group having 1 to 20 carbon atoms, a straight chain or branched heteroalkylene group having 1 to 20 carbon atoms, a straight chain or branched alkenylene group having 2 to 20 carbon atoms, a cycloalkylene group having 3 to 20 carbon atoms, a heterocycloalkylene group having 3 to 20 carbon atoms, an alkyleneoxy group having 1 to 20 carbon atoms, an alkylene ester group having 1 to 20 carbon atoms, an arylene group having 6 to 12 carbon atoms, an aryl alkylene group having 6 to 20 carbon atoms, or a heteroarylene group having 4 to 10 carbon atoms.

[0107] For example, the compound represented by the above Chemical Formula 2 may be a compound represented by any one of the following Chemical Formulas 2-1 to 2-46.

[0108] [Chemical formula 2-1]

[0109]

[0110] [Chemical formula 2-2]

[0111]

[0112] [Chemical formula 2-3]

[0113]

[0114] [Chemical formula 2-4]

[0115]

[0116] [Chemical formula 2-5]

[0117]

[0118] [Chemical formula 2-6]

[0119]

[0120] [Chemical formula 2-7]

[0121]

[0122] [Chemical formula 2-8]

[0123]

[0124] [Chemical formula 2-9]

[0125]

[0126] [Chemical formula 2-10]

[0127]

[0128] [Chemical formula 2-11]

[0129]

[0130] [Chemical formula 2-12]

[0131]

[0132] [Chemical formula 2-13]

[0133]

[0134] [Chemical formula 2-14]

[0135]

[0136] [Chemical formula 2-15]

[0137]

[0138] [Chemical formula 2-16]

[0139]

[0140] [Chemical formula 2-17]

[0141]

[0142] [Chemical formula 2-18]

[0143]

[0144] [Chemical formula 2-19]

[0145]

[0146] [Chemical formula 2-20]

[0147]

[0148] [Chemical formula 2-21]

[0149]

[0150] [Chemical formula 2-22]

[0151]

[0152] [Chemical formula 2-23]

[0153] [Chemical formula 2-24]

[0154]

[0155] [Chemical formula 2-25]

[0156]

[0157] [Chemical formula 2-26]

[0158]

[0159] [Chemical formula 2-27]

[0160]

[0161] [Chemical formula 2-28]

[0162]

[0163] [Chemical formula 2-29]

[0164]

[0165] [Chemical formula 2-30]

[0166]

[0167] [Chemical formula 2-31]

[0168]

[0169] [Chemical formula 2-32]

[0170]

[0171] [Chemical formula 2-33]

[0172] [Chemical formula 2-34]

[0173]

[0174] [Chemical formula 2-35]

[0175]

[0176] [Chemical formula 2-36]

[0177]

[0178] [Chemical formula 2-37]

[0179]

[0180] [Chemical formula 2-38]

[0181]

[0182] [Chemical formula 2-39]

[0183]

[0184] [Chemical formula 2-40]

[0185]

[0186] [Chemical formula 2-41]

[0187]

[0188] [Chemical formula 2-42]

[0189]

[0190] [Chemical formula 2-43]

[0191]

[0192] [Chemical formula 2-44]

[0193]

[0194] [Chemical formula 2-45]

[0195]

[0196] [Chemical formula 2-46]

[0197]

[0198] [Chemical formula 3]

[0199]

[0200] In the above chemical formula 3, R3 can be hydrogen or methyl, R4 can be a straight chain or branched alkylene group having 1 to 30 carbon atoms, a straight chain or branched alkenylene group having 2 to 30 carbon atoms, a cycloalkylene group having 3 to 30 carbon atoms, a heterocycloalkylene group having 3 to 30 carbon atoms, an alkyleneoxy group having 1 to 30 carbon atoms, an alkylene ester group having 1 to 30 carbon atoms, an arylene group having 6 to 20 carbon atoms, an arylalkylene group having 6 to 30 carbon atoms, or a heteroarylene group having 4 to 20 carbon atoms, and m can be an integer of 1 to 100.

[0201] Preferably, the above R4 can be a straight chain or branched alkylene group having 1 to 20 carbon atoms, a straight chain or branched alkenylene group having 2 to 20 carbon atoms, a cycloalkylene group having 3 to 20 carbon atoms, a heterocycloalkylene group having 3 to 20 carbon atoms, an alkyleneoxy group having 1 to 20 carbon atoms, an alkylene ester group having 1 to 20 carbon atoms, an arylene group having 6 to 12 carbon atoms, an aryl alkylene group having 6 to 20 carbon atoms, or a heteroarylene group having 4 to 10 carbon atoms, and m can be an integer of 1 to 50.

[0202] For example, the compound represented by the above Chemical Formula 3 may be a compound represented by any one of the following Chemical Formulas 3-1 to 3-15.

[0203] [Chemical formula 3-1]

[0204]

[0205] [Chemical formula 3-2]

[0206]

[0207] [Chemical formula 3-3]

[0208]

[0209] [Chemical formula 3-4]

[0210]

[0211] [Chemical formula 3-5]

[0212]

[0213] [Chemical formula 3-6]

[0214]

[0215] [Chemical formula 3-7]

[0216]

[0217] [Chemical formula 3-8]

[0218]

[0219] [Chemical formula 3-9]

[0220]

[0221] [Chemical formula 3-10]

[0222]

[0223] [Chemical formula 3-11]

[0224]

[0225] [Chemical formula 3-12]

[0226]

[0227] [Chemical formula 3-13]

[0228]

[0229] [Chemical formula 3-14]

[0230]

[0231] [Chemical formula 3-15]

[0232]

[0233] In the present invention, when m in the above Chemical Formula 3 is 1, the compound represented by Chemical Formula 3 can be represented by the compound represented by Chemical Formula 2 according to the selection of substituents, and the compound represented by Chemical Formula 2 can also be represented by the compound represented by Chemical Formula 3 according to the selection of substituents.

[0234] In addition, when the compound represented by Chemical Formula 2 and the compound represented by Chemical Formula 3 are used in combination, when R2 in Chemical Formula 2 is an alkylene ester having 3 to 30 carbon atoms, m in Chemical Formula 3 may not be 1.

[0235] [Chemical formula 4]

[0236]

[0237] In the above chemical formula 4, R5 is hydrogen or methyl, and R6 can be a linear or branched alkylene group having 1 to 30 carbon atoms, or an alkylene group containing ester or amide. Preferably, R6 can be a linear or branched alkylene group having 1 to 20 carbon atoms, or an alkylene group containing ester or amide.

[0238] In addition, in the above chemical formula 4, A may be -O-, -NH- or -NR7-, R7 may be an alkyl group having 1 to 10 carbon atoms, and l may be an integer from 1 to 250. Preferably, the above A is -O- or -NH-, and l may be an integer from 1 to 200.

[0239] In the above chemical formula 4, when l is greater than the above range, the viscosity of the composition including quantum dots may be affected.

[0240] The compound represented by the above chemical formula 4 has a thiol group, which can be bonded to the surface of the quantum dot. Compared with the ligand layer compounds of common quantum dots such as carboxylic acids, the thiol group has the following advantages: excellent bonding force with the surface of the quantum dot, suppressing the extinction caused by surface defects such as the unsaturated bond of the quantum dot and the extinction caused by oxidation, thereby improving the optical properties (luminescence properties) and reliability.

[0241] In one embodiment of the present invention, the compound represented by the above Chemical Formula 4 may be a compound represented by any one of the following Chemical Formulas 4-1 to 4-4.

[0242] [Chemical formula 4-1]

[0243]

[0244] In the above chemical formula 4-1, la may be an integer of 1 to 200.

[0245] [Chemical formula 4-2]

[0246]

[0247] In the above chemical formula 4-2, lb may be an integer of 1 to 200.

[0248] [Chemical formula 4-3]

[0249]

[0250] In the above chemical formula 4-3, lc may be an integer of 1 to 200.

[0251] [Chemical formula 4-4]

[0252]

[0253] In the above chemical formula 4-4, ld may be an integer of 1 to 200.

[0254] The compounds represented by the above Chemical Formulae 1 to 4 of the present invention can function as organic ligands to coordinate and bind to the surface of quantum dots to stabilize the quantum dots.

[0255] In general, the quantum dots usually manufactured have a ligand layer on the surface. Immediately after manufacture, the ligand layer may be composed of oleic acid, lauric acid, 2-(2-methoxyethoxy)acetic acid, 2-[2-(2-methoxyethoxy)ethoxy]acetic acid and succinic acid mono-[2-(2-methoxy-ethoxy)-ethyl] ester, etc. At this time, compared with the quantum dots of the present invention containing one or more of the compounds represented by the above-mentioned Chemical Formulas 1 to 4 as the ligand layer, the surface protection effect may be reduced due to the non-binding defects on the surface of the quantum dots due to the weaker binding force between the ligand layer and the quantum dots. In addition, with respect to oleic acid, it is easy to disperse in saturated hydrocarbon solvents such as n-hexane, which are highly volatile organic compounds (VOCs), and aromatic solvents such as chloroform and benzene, but has poor dispersibility in solvents such as PGMEA.

[0256] The quantum dots of the present invention include one or more compounds represented by Chemical Formulas 1 to 4 in the ligand layer, so that the surface of the quantum dots is protected and they can exhibit excellent oxidative stability compared to previous quantum dots. In addition, they have very excellent dispersibility in solvents such as PGMEA and exhibit the effect of improving optical properties.

[0257] In some embodiments, the quantum dots of the present invention contain one or more compounds represented by the above-mentioned Chemical Formulas 1 to 4 in the ligand layer, and may further contain oleic acid, lauric acid, 2-(2-methoxyethoxy)acetic acid, 2-[2-(2-methoxyethoxy)ethoxy]acetic acid and succinic acid mono-[2-(2-methoxy-ethoxy)-ethyl] ester, etc.

[0258] The quantum dots are not particularly limited as long as they can emit light through stimulation by light or electricity. For example, they can be selected from the group consisting of II-VI semiconductor compounds; III-V semiconductor compounds; IV-VI semiconductor compounds; IV elements or compounds containing them; and combinations thereof, and they can be used alone or in combination of two or more.

[0259] Quantum dots can be a homogeneous single structure; a dual structure such as a core-shell structure and a gradient structure; or a mixed structure thereof. In the present invention, the type of quantum dots is not particularly limited as long as they can emit light through stimulation by light.

[0260] According to one embodiment, the quantum dot has a core-shell structure, and the core may include one or more selected from the group consisting of InP, InZnP, InGaP, CdSe, CdS, CdTe, ZnS, ZnSe, ZnTe, CdSeTe, CdZnS, CdSeS, PbSe, PbS, PbTe, AgInZnS, HgS, HgSe, HgTe, GaN, GaP, GaAs, InGaN, InAs and ZnO, and the shell may include one or more selected from the group consisting of ZnS, ZnSe, ZnTe, ZnO , CdS, CdSe, CdTe, CdO, InP, InS, GaP, GaN, GaO, InZnP, InGaP, InGaN, InZnSCdSe, PbS, TiO, SrSe and HgSe. Preferably, it may include one or more selected from the group consisting of InP / ZnS, InP / ZnSe, InP / GaP / ZnS, InP / ZnSe / ZnS, InP / ZnSeTe / ZnS and InP / MnSe / ZnS, but is not limited to this.

[0261] Generally speaking, quantum dots can be manufactured by a wet chemical process, a metal organic chemical vapor deposition (MOCVD) process, or a molecular beam epitaxy (MBE) process.

[0262] The quantum dots of the present invention can be synthesized by wet chemical processes.

[0263] The above-mentioned wet chemical process is a method of adding precursor substances to an organic solvent to grow particles. When the crystals grow, the organic solvent naturally coordinates to the surface of the quantum dot crystals and plays the role of a dispersant, thereby controlling the growth of the crystals. Therefore, compared with organic metal chemical vapor deposition processes or vapor phase deposition methods such as molecular beam epitaxy, the size growth of quantum dot particles can be controlled through an easier and cheaper process.

[0264] When quantum dots are produced by a wet chemical process, an organic ligand is used to prevent aggregation of quantum dots and control the particle size of the quantum dots to a nanometer level. As such an organic ligand, oleic acid is generally used.

[0265] In one embodiment of the present invention, the oleic acid used in the process of manufacturing the quantum dots is replaced with one or more compounds represented by Chemical Formulae 1 to 4 through a ligand exchange method.

[0266] The ligand exchange is carried out as follows: the organic ligand to be exchanged, i.e., one or more compounds represented by Chemical Formulae 1 to 4, is added to a dispersion containing quantum dots having the original organic ligand, i.e., oleic acid, and then stirred at room temperature to 200° C. for 30 minutes to 3 hours to obtain quantum dots bound with one or more compounds represented by Chemical Formulae 1 to 4. If necessary, a process of separating and purifying the quantum dots bound with one or more compounds represented by Chemical Formulae 1 to 4 may be further carried out.

[0267] As described above, the quantum dots according to one embodiment of the present invention have the advantage that they can be produced in large quantities by an organic ligand exchange method that involves a simple stirring process at room temperature.

[0268] Furthermore, the quantum dots according to one embodiment of the present invention can maintain a quantum efficiency of about 85% or more compared to the initial quantum efficiency even after 15 days, and thus can be stably stored for a long period of time and can be commercialized for a variety of uses.

[0269] <Quantum dot dispersion>

[0270] One embodiment of the present invention relates to a quantum dot dispersion. The quantum dot dispersion of the present invention comprises the above-mentioned quantum dots and at least one selected from a monomer and a solvent.

[0271] In the present invention, the content of the quantum dots can be 10 to 95 parts by weight, preferably 20 to 90 parts by weight, and more preferably 20 to 80 parts by weight, relative to 100 parts by weight of the solid component of the quantum dot dispersion. When the content of the quantum dots is within the above range, a quantum dot light conversion composition or a self-luminous photosensitive resin composition having excellent luminescent properties can be provided. When the content of the quantum dots is less than the above content range, the optical properties may decrease, making it difficult to achieve a high-quality display device. In addition, when the content is greater than the above content range, insufficient components for achieving curing or developing properties may result in the failure to form a pattern, or insufficient degree of curing of the coating may reduce the productivity of the post-manufacturing process of the display and the reliability of the product.

[0272] The monomer contained in the quantum dot dispersion of the present invention is a dispersing monomer that plays a role in dispersing the quantum dots.

[0273] Examples of the dispersing monomer used in the present invention include monofunctional monomers, difunctional monomers, and other polyfunctional monomers, and preferably difunctional or higher-functional monomers are used.

[0274] The type of the monofunctional monomer is not particularly limited, and examples thereof include nonylphenyl carbitol acrylate, 2-hydroxy-3-phenoxypropyl acrylate, 2-ethylhexyl carbitol acrylate, and 2-hydroxyethyl acrylate.

[0275] The type of the bifunctional monomer is not particularly limited, and examples thereof include 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, ethylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, bis(acryloyloxyethyl) ether of bisphenol A, and 3-methylpentanediol di(meth)acrylate.

[0276] The type of the above-mentioned multifunctional monomer is not particularly limited, and examples thereof include trimethylolpropane tri(meth)acrylate, ethoxylated trimethylolpropane tri(meth)acrylate, propoxylated trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol tri(meth)acrylate, dipentaerythritol penta(meth)acrylate, ethoxylated dipentaerythritol hexa(meth)acrylate, propoxylated dipentaerythritol hexa(meth)acrylate, and dipentaerythritol hexa(meth)acrylate.

[0277] The content of the dispersing monomer may be 10 to 90 parts by weight, preferably 20 to 80 parts by weight, and more preferably 30 to 70 parts by weight, relative to 100 parts by weight of the solid content in the entire quantum dot dispersion.

[0278] If the content is less than the above range, the dispersion characteristics will be reduced or the coating or spraying characteristics may deteriorate due to the high viscosity of the dispersion. On the contrary, if it is greater than the above range, the light source absorption rate of the quantum dots is insufficient, the color reproducibility is reduced, and the luminous efficiency performance is reduced, so that the optical properties may be reduced.

[0279] The quantum dots of the present invention can be dispersed using a solvent.

[0280] As the above-mentioned solvent, there can be mentioned alkylene glycol monoalkyl ethers such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monopropyl ether, and ethylene glycol monobutyl ether; diethylene glycol dialkyl ethers such as diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dipropyl ether, and diethylene glycol dibutyl ether; methyl cellosolve acetate, ethyl cellosolve acetate, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, propylene glycol monopropyl ether acetate, methoxybutyl acetate, and n-pentyl acetate. In the present invention, the solvent can be used alone or in combination with the above-mentioned monomers.

[0281] In 100 parts by weight of the quantum dot dispersion as a whole, the content of the above solvent may be 10 to 90 parts by weight, preferably 20 to 80 parts by weight. When the content of the solvent is less than the above range, the dispersion characteristics are reduced, the film-forming characteristics caused by foreign matter may be reduced, and the luminescence characteristics may be deteriorated. When the content is greater than the above range, the color area of ​​the display may decrease due to insufficient luminous intensity and light leakage of the light source, so it is preferred to meet the above range.

[0282] The quantum dots (QD) dispersion may be dispersed in a monomer or a solvent as a single component. Alternatively, the quantum dots (QD) dispersion may be produced by mixing a monomer and a solvent and dispersing the quantum dots therein.

[0283] In the present invention, when the solvent and the monomer are mixed for use, the content of the solvent may be 0.1 to 100 parts by weight relative to 100 parts by weight of the solvent and the monomer as a whole. More preferably, it may be 20 to 80 parts by weight. When the content is within the above range, the dispersibility and viscosity stability are improved and the storage stability is excellent, the film-forming properties are excellent and the productivity can be improved, and a high-quality self-luminous display can be provided due to the excellent color range and brightness.

[0284] <Quantum dot light conversion composition>

[0285] The quantum dot light conversion composition of the present invention comprises the above-mentioned quantum dot dispersion and may further comprise one or more selected from a photopolymerizable compound, a photopolymerization initiator, scattering particles and a solvent, and may further comprise constituent components such as additives known in the art as required.

[0286] In one embodiment, the above-mentioned components that can be added to the quantum dot light conversion composition of the present invention can be used as components that can be added to the self-luminous photosensitive resin composition described later.

[0287] Hereinafter, each component contained in the quantum dot light conversion composition of the present invention will be described in detail.

[0288] Quantum dot dispersion

[0289] The quantum dot dispersion contained in the quantum dot light conversion composition of the present invention directly uses the above-mentioned quantum dot dispersion.

[0290] When the quantum dot dispersion is added to the quantum dot light conversion composition of the present invention, the content may be 10 to 90 parts by weight, preferably 20 to 80 parts by weight, relative to 100 parts by weight of the entire composition.

[0291] When the quantum dot light conversion composition of the present invention contains the quantum dot dispersion in the above content range, the light emitting characteristics and coating film formability are excellent.

[0292] In the present invention, the description of the quantum dot dispersion described above is also applied similarly to the quantum dot dispersion contained in the self-luminous photosensitive resin composition described later.

[0293] Photopolymerizable compounds

[0294] The photopolymerizable compound in the present invention is a compound that can be polymerized by the action of light and a photopolymerization initiator described below, and examples thereof include monofunctional monomers, difunctional monomers, and other polyfunctional monomers, and preferably difunctional or higher-functional monomers are used.

[0295] The type of the monofunctional monomer is not particularly limited, and examples thereof include nonylphenyl carbitol acrylate, 2-hydroxy-3-phenoxypropyl acrylate, 2-ethylhexyl carbitol acrylate, 2-hydroxyethyl acrylate, and N-vinyl pyrrolidone.

[0296] The type of the bifunctional monomer is not particularly limited, and examples thereof include 1,6-hexanediol di(meth)acrylate, ethylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, bis(acryloyloxyethyl) ether of bisphenol A, and 3-methylpentanediol di(meth)acrylate.

[0297] The type of the above-mentioned multifunctional monomer is not particularly limited, and examples thereof include trimethylolpropane tri(meth)acrylate, ethoxylated trimethylolpropane tri(meth)acrylate, propoxylated trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol tri(meth)acrylate, dipentaerythritol penta(meth)acrylate, ethoxylated dipentaerythritol hexa(meth)acrylate, propoxylated dipentaerythritol hexa(meth)acrylate, and dipentaerythritol hexa(meth)acrylate.

[0298] The content of such a photopolymerizable compound may be 1 to 45 parts by weight, preferably 1 to 20 parts by weight, relative to 100 parts by weight of the entire composition. If the content is less than the above range, the photosensitivity may be reduced. On the contrary, if the content is greater than the above range, the adhesion between the quantum dot light conversion layer and the self-luminous photosensitive resin layer is too large and the strength of the film is insufficient, and the pattern may be lost during development.

[0299] In the present invention, the description of the above-mentioned photopolymerizable compound is also applied similarly to the photopolymerizable compound contained in the self-luminous photosensitive resin composition described later.

[0300] Photopolymerization initiator

[0301] The photopolymerization initiator in the present invention is a compound used to initiate the polymerization of the photopolymerizable compound described above. There is no particular limitation in the present invention, and acetophenone-based, benzophenone-based, triazine-based, thioxanthone-based, oxime-based, benzoin-based, anthracene-based, anthraquinone-based and biimidazole-based compounds can be used. They can be used alone or in combination of two or more.

[0302] For example, the benzophenone compound may be benzophenone, benzoylbenzoic acid, methyl benzoylbenzoate, 4-phenylbenzophenone, hydroxybenzophenone, acrylated benzophenone, 4,4'-bis(dimethylamino)benzophenone, 4,4'-bis(diethylamino)benzophenone, or the like.

[0303] As other photopolymerization initiators, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, 10-butyl-2-chloroacridone, 9,10-phenanthrenequinone, camphorquinone, methyl phenylglyoxylate, titanocene compounds, and the like can be used.

[0304] The content of the photopolymerization initiator may be 0.1 to 20 parts by weight, preferably 0.5 to 15 parts by weight, based on 100 parts by weight of the entire composition.

[0305] If the content of the above-mentioned photopolymerization initiator is within the above-mentioned range, there is a tendency that the quantum dot light conversion composition and / or the self-luminous photosensitive resin composition has high sensitivity and the strength of the pixel portion or the smoothness of the surface of the pixel portion becomes better, so it is preferred. In addition, if the content of the photopolymerization initiator auxiliary is within the above-mentioned range, there is a tendency that the sensitivity efficiency of the quantum dot light conversion composition and / or the self-luminous photosensitive resin composition becomes further higher, and the productivity of the color filter formed using the composition is improved, so it is preferred.

[0306] In the present invention, the description of the above-mentioned photopolymerization initiator is also applied similarly to the photopolymerization initiator contained in the self-luminous photosensitive resin composition described later.

[0307] Solvents

[0308] The solvent is not particularly limited in the present invention as long as it can dissolve or disperse the above-mentioned composition. Representative examples include alkylene glycol monoalkyl ethers, alkylene glycol alkyl ether acetates, aromatic hydrocarbons, ketones, lower and higher alcohols, and sulfonic acid esters.

[0309] More specifically, examples of the solvent include alkylene glycol monoalkyl ethers such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monopropyl ether, and ethylene glycol monobutyl ether; diethylene glycol dialkyl ethers such as diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dipropyl ether, and diethylene glycol dibutyl ether; methyl cellosolve acetate, ethyl cellosolve acetate, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, propylene glycol monobutyl ether; Alkylene glycol alkyl ether acetates such as monopropyl ether acetate, methoxybutyl acetate and methoxypentyl acetate; aromatic hydrocarbons such as benzene, toluene, xylene, mesitylene, etc.; ketones such as methyl ethyl ketone, acetone, methyl amyl ketone, methyl isobutyl ketone, cyclohexanone, etc.; alcohols such as ethanol, propanol, butanol, hexanol, cyclohexanol, ethylene glycol, glycerol, etc.; esters such as ethyl 3-ethoxypropionate and methyl 3-methoxypropionate; cyclic esters such as γ-butyrolactone, etc.

[0310] From the perspective of coating and drying properties, the above solvents preferably include organic solvents having a boiling point of 100 to 200° C., more preferably include esters such as alkylene glycol alkyl ether acetates, ketones, 3-ethoxyethyl propionate, and 3-methoxymethyl propionate, and more preferably include propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, cyclohexanone, 3-ethoxyethyl propionate, and 3-methoxymethyl propionate. These solvents may be used alone or in combination of two or more.

[0311] The content of such a solvent may be the balance to satisfy 100 parts by weight of the entire composition. Such a content is a range selected in consideration of the dispersion stability of the composition and the ease of the process (for example, coating properties) in the production process.

[0312] In the present invention, the description about the above solvent is also applied similarly to the solvent contained in the self-luminous photosensitive resin composition described later.

[0313] Scattering particles

[0314] The quantum dot light conversion composition of the present invention may contain scattering particles. The scattering particles may be made of common inorganic materials, and preferably may contain metal oxides having an average particle size of 30 to 1000 nm.

[0315] The above-mentioned metal oxide can be an oxide of a metal selected from the group consisting of Li, Be, B, Na, Mg, Al, Si, K, Ca, Sc, V, Cr, Mn, Fe, Ni, Cu, Zn, Ga, Ge, Rb, Sr, Y, Mo, Cs, Ba, La, Hf, W, Tl, Pb, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Ti, Sb, Sn, Zr, Nb, Ce, Ta, In and combinations thereof, but is not limited thereto.

[0316] Specifically, it can be one selected from the group consisting of Al2O3, SiO2, ZnO, ZrO2, BaTiO3, TiO2, Ta2O5, Ti3O5, ITO, IZO, ATO, ZnO-Al, Nb2O3, SnO, MgO and combinations thereof. If necessary, a material surface-treated with a compound having an unsaturated bond such as acrylate can also be used.

[0317] When the quantum dot light conversion composition of the present invention contains scattering particles, the scattering particles can increase the path of light spontaneously released from the quantum dots and improve the overall light efficiency of the color filter, which is preferred.

[0318] Preferably, the scattering particles may have an average particle size of 30 to 1000 nm, preferably 100 to 500 nm. At this time, if the particle size is too small, sufficient scattering effect of light released from the quantum dots cannot be expected, and on the contrary, if it is too large, it will be deposited in the composition, or a uniform quality of the self-luminous layer surface cannot be obtained, so it is appropriately adjusted within the above range.

[0319] The scattering particles can be used in an amount of 0.1 to 50 parts by weight, preferably 0.5 to 30 parts by weight, relative to 100 parts by weight of the quantum dot light conversion composition as a whole. When the content of the scattering particles is within the above range, the luminous intensity increase effect can be maximized, so it is preferred. When the content of the scattering particles is less than the above range, it is difficult to ensure the desired luminous intensity. When the content is greater than the above range, not only can no further luminous intensity increase effect be obtained, but also the stability of the composition may be reduced. Therefore, it is preferably used appropriately within the above range.

[0320] In the present invention, the description of the scattering particles described above can also be similarly applied to the scattering particles contained in the self-luminous photosensitive resin composition described later.

[0321] additive

[0322] The quantum dot light conversion composition of the present invention may further contain known additives for various purposes. Such additives include fillers, other polymer compounds, curing agents, adhesion promoters, antioxidants, ultraviolet absorbers, anti-coagulants and other additives. These additives can be used alone or in combination, and are preferably used in an amount of less than 1% by weight in the overall composition, taking into account light efficiency and the like.

[0323] In the present invention, the description of the above-mentioned additives can also be similarly applied to the additives contained in the self-luminous photosensitive resin composition described later.

[0324] The quantum dot light conversion composition of the present invention can be preferably used for the manufacture of a color filter and an image display device including the same.

[0325] <Self-luminous photosensitive resin composition>

[0326] In the present invention, the quantum dot light conversion composition described above can be used as a self-luminous photosensitive resin composition by further including a carboxyl group-containing alkali-soluble resin in the components contained in the composition.

[0327] For example, the self-luminous photosensitive resin composition of the present invention includes the above-mentioned quantum dot dispersion. In addition, it further includes one or more selected from photopolymerizable compounds, photopolymerization initiators, scattering particles and solvents as components that can be added to the quantum dot light conversion composition, and in addition, it includes an alkali-soluble resin. If necessary, it may also further include constituent components such as additives known in the technical field.

[0328] As described above, the quantum dot dispersion, photopolymerizable compound, photopolymerization initiator, scattering particles, solvent and additive components contained in the self-luminous photosensitive resin composition of the present invention have the same structure as the quantum dot dispersion, photopolymerizable compound, photopolymerization initiator, scattering particles, solvent and additive components contained in the above-mentioned quantum dot light conversion composition.

[0329] Hereinafter, the remaining components other than the components contained in the quantum dot light conversion composition described above, that is, the alkali-soluble resin contained in the self-luminous photosensitive resin composition of the present invention will be described in detail.

[0330] Alkali soluble resin

[0331] The alkali-soluble resin contained in the self-luminous photosensitive resin composition of the present invention includes at least one of a Cardo-based alkali-soluble resin and an acrylic alkali-soluble resin.

[0332] In the present invention, the Cardo-based alkali-soluble resin may include at least one repeating unit of the following Chemical Formula 5 to the following Chemical Formula 8.

[0333] [Chemical formula 5]

[0334]

[0335] [Chemical formula 6]

[0336]

[0337] [Chemical formula 7]

[0338]

[0339] [Chemical formula 8]

[0340]

[0341] In the above chemical formulas 5 to 8,

[0342] X and X' are each independently a single bond, -CO-, -SO2-, -C(CF3)2-, -Si(CH3)2-, -CH2-, -C(CH3)2-, -O-,

[0343]

[0344] Y is an anhydride residue,

[0345] Z is an acid dianhydride residue,

[0346] R' is a hydrogen atom, an ethyl group, a phenyl group, -C2H4Cl, -C2H4OH or -CH2CH=CH2,

[0347] R1, R1', R2, R2', R3, R3', R4, R4', R5, R5', R6 and R6' are each independently a hydrogen atom or a methyl group,

[0348] R7, R7', R8 and R8' are each independently a linear or branched alkylene group having 1 to 6 carbon atoms, wherein the alkylene group may be interrupted by at least one of an ester bond, a cycloalkylene group having 6 to 14 carbon atoms and an arylene group having 6 to 14 carbon atoms,

[0349] R9, R9', R10, R10', R11, R11', R12 and R12' are each independently a hydrogen atom, a halogen atom or a linear or branched alkyl group having 1 to 5 carbon atoms,

[0350] m and n are each integers satisfying 0≤m≤30, 0≤n≤30, wherein m and n are not 0 at the same time.

[0351] Preferably, the above R7, R7', R8 and R8' are each independently a linear or branched alkylene group having 1 to 6 carbon atoms, and the above alkylene group may be interrupted by at least one of an ester bond, a cycloalkylene group having 6 to 14 carbon atoms, and an arylene group having 6 to 14 carbon atoms, preferably an ethylene group, Better.

[0352] When the self-luminous photosensitive resin composition of the present invention includes a cardo-based alkali-soluble resin including at least one repeating unit among the repeating units of the above Chemical Formulae 5 to 8, there is an advantage that inter-process reliability is improved.

[0353] When the Cardo-based alkali-soluble resin of the present invention contains two or more or all of the repeating units of the above Chemical Formulae 5 to 8, the molar ratio is not particularly limited. For example, when the above Cardo-based alkali-soluble resin contains two repeating units, the molar ratio of the repeating units may be, for example, 1 / 99 to 90 / 10, more preferably 5 / 95 to 80 / 20. Preferably, the molar ratio of the above repeating units may be m / n.

[0354] When the molar ratio of the repeating units, specifically m / n, satisfies the above range, the carboxyl content of the alkali-soluble resin is appropriately maintained to maintain good alkali resistance, and the developing solution is not eluted in the exposed portion, thereby exhibiting excellent alkali developability and forming a fine pattern.

[0355] In the above chemical formulas 5 and 7, Y is an acid anhydride residue, which can be obtained by reacting a bisphenol epoxy acrylate compound, which is a synthetic intermediate of the Cardo-based alkali-soluble resin of the present invention, with an acid anhydride compound. The acid anhydride compound into which the residue Y can be introduced is not particularly limited, and examples thereof include maleic anhydride, succinic anhydride, itaconic anhydride, phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methylendomethylenetetrahydrophthalic anhydride, chloric anhydride, methyltetrahydrophthalic anhydride, and the like.

[0356] In the above chemical formulas 6 and 8, Z is a residue of an acid dianhydride, which can be obtained by reacting a bisphenol epoxy acrylate compound, which is a synthetic intermediate of the Cardo-based alkali-soluble resin of the present invention, with an acid dianhydride compound. The acid dianhydride compound into which the residue Z can be introduced is not particularly limited, and examples thereof include aromatic polycarboxylic acid anhydrides such as pyromellitic anhydride, benzophenone tetracarboxylic anhydride, biphenyl tetracarboxylic anhydride, and diphenyl ether tetracarboxylic anhydride.

[0357] In the present invention, "single bond" means a structure in which no other functional groups are directly connected. For example, in the above chemical formulas 5 to 8, there are no X and X', and oxyphenyl groups are directly connected.

[0358] In the present invention, "acid dianhydride" means a compound containing two acid anhydride groups in the molecule.

[0359] In the present invention, the method for producing the Cardo-based alkali-soluble resin polymerized by containing any one of the repeating units represented by the above Chemical Formulae 5 to 8 is not particularly limited.

[0360] For example, a bisphenol compound can be reacted with an epoxy compound to synthesize a bisphenol epoxy compound, and then the synthesized bisphenol epoxy compound can be reacted with an acrylate compound to synthesize a bisphenol epoxy acrylate compound, and then the bisphenol epoxy acrylate compound can be reacted with an acid anhydride, an acid dianhydride or a mixture thereof to produce the bisphenol epoxy acrylate. The bisphenol epoxy acrylate can be reacted with at least one selected from the group consisting of maleic anhydride, succinic anhydride, itaconic anhydride, phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methylendomethylenetetrahydrophthalic anhydride, chloric anhydride, and methyltetrahydrophthalic anhydride as specific compounds, or selected from the group consisting of aromatic polycarboxylic acid anhydrides such as pyromellitic anhydride, benzophenonetetracarboxylic anhydride, biphenyltetracarboxylic anhydride, and diphenyl ether tetracarboxylic anhydride as acid dianhydrides to produce the bisphenol epoxy acrylate, but the present invention is not limited to this.

[0361] Preferably, the Cardo-based alkali-soluble resin of the present invention may be polymerized by containing a compound represented by the following Chemical Formula 9 or a compound represented by the following Chemical Formula 10.

[0362]

[0363] In the above chemical formulas 9 and 10,

[0364] R15 to R18 are each independently

[0365] A' is hydrogen, an alkyl group having 1 to 5 carbon atoms, or a hydroxyl group,

[0366] R19 is hydrogen or an alkyl group having 1 to 5 carbon atoms.

[0367] When the alkali-soluble resin of the present invention includes a Cardo-based alkali-soluble resin polymerized by containing the compound represented by the above Chemical Formula 9, it has the advantages of being able to improve the adhesion to the substrate, being excellent in development adhesion, and being able to realize a fine pattern for high resolution.

[0368] The compound represented by the above Chemical Formula 9 can be synthesized using the following Chemical Formula 11, and by further reacting an acid anhydride or an acid dianhydride compound with the compound, an alkali-soluble Cardo-based alkali-soluble resin can be obtained.

[0369]

[0370] For example, it can be manufactured as follows, but is not limited to this: the compound represented by the above chemical formula 11 is mixed with epichlorohydrin and tert-butylammonium bromide, and then heated with a solvent for reaction, and then an alkaline aqueous solution is added dropwise and precipitated and separated to synthesize an epoxy compound, and then the synthesized epoxy compound is mixed with tert-butylammonium bromide, acrylic acid, a phenolic compound and a solvent for reaction, and the obtained compound is reacted with at least one selected from the group consisting of maleic anhydride, succinic anhydride, itaconic anhydride, phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methylendomethylenetetrahydrophthalic anhydride, chloric anhydride, methyltetrahydrophthalic anhydride or the group consisting of aromatic polycarboxylic acid anhydride such as pyromellitic anhydride, benzophenonetetracarboxylic anhydride, biphenyltetracarboxylic anhydride, and diphenyl ether tetracarboxylic anhydride.

[0371] In addition, when the alkali-soluble resin of the present invention includes a Cardo-based alkali-soluble resin obtained by polymerizing a compound represented by the following Chemical Formula 10, the adhesiveness to the substrate is improved, the development adhesion is excellent, and a fine pattern for high resolution can be realized.

[0372]

[0373] In the formula, R17 and R18 are each independently

[0374] A' is a hydrogen atom, an alkyl group having 1 to 5 carbon atoms, or a hydroxyl group, and R19 is a hydrogen atom or an alkyl group having 1 to 5 carbon atoms. Preferably, A' is a hydroxyl group, and R19 is a hydrogen atom or a methyl group.

[0375] The compound represented by the above Chemical Formula 10 can be synthesized using the following Chemical Formula 12, and by reacting an acid anhydride or an acid dianhydride compound with the compound, an alkali-soluble Cardo-based alkali-soluble resin can be obtained.

[0376]

[0377]

[0378] For example, it can be manufactured as follows, but is not limited to this: the compound represented by the above chemical formula 12 is mixed with epichlorohydrin, tert-butylammonium bromide, and a solvent, and the mixture is heated to react, and then an alkaline aqueous solution is added dropwise to precipitate and separate to synthesize an epoxy compound, and then the synthesized epoxy compound is mixed with tert-butylammonium bromide, acrylic acid, a phenolic compound, and a solvent to react, and the obtained compound is reacted with at least one selected from the group consisting of maleic anhydride, succinic anhydride, itaconic anhydride, phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methylendomethylenetetrahydrophthalic anhydride, chloric anhydride, and methyltetrahydrophthalic anhydride as acid anhydrides, or selected from the group consisting of aromatic polycarboxylic acid anhydrides such as pyromellitic anhydride, benzophenonetetracarboxylic anhydride, biphenyltetracarboxylic anhydride, and diphenyl ether tetracarboxylic anhydride as acid dianhydrides.

[0379] In the above chemical formulas 11 and 12, the position of the hydroxyl group (—OH) is not particularly limited, and may be, for example, the 2-position, 3-position, and 4-position, preferably the 4-position (the position is determined by setting the carbon bonded to the xanthene to the 1-position).

[0380] As a result, according to the position of the hydroxyl group (—OH) of Chemical Formula 11 or 12, the substitution positions of R15 to R18 of the above Chemical Formulas 9 and 10 may be determined.

[0381] More specific examples of the compound represented by the above chemical formula 9 or 10 may be selected from 9,9-bis(3-cinnamic diester)fluorene, 9,9-bis(3-cinnamoyl,4-hydroxyphenyl)fluorene, 9,9-bis(glycidyl methacrylate ether)fluorene, 9,9-bis(3,4-dihydroxyphenyl)fluorene dicinnamic ester, 3,6-diglycidyl methacrylate ether, spiro(fluorene-9,9-xanthene), 9,9-bis(glycidyl methacrylate ether)fluorene, 9,9-bis(3,4-dihydroxyphenyl)fluorene dicinnamic ester, 3,6-diglycidyl methacrylate ether, 9,9-bis(3,4-dihydroxyphenyl)fluorene dicinnamic ester ... At least one of the group consisting of 9,9-bis(3-allyl,4-hydroxyphenylfluorene), 9,9-bis(4-allyloxyphenyl)fluorene, and 9,9-bis(3,4-methacrylic diester)fluorene, but not limited thereto.

[0382] The acid value of the Cardo-based alkali-soluble resin may be 10 to 200 mgKOH / g, and preferably 30 to 150 mgKOH / g. When the acid value is within the above range, a sufficient development speed can be ensured, thereby realizing a fine pattern for high resolution.

[0383] The weight average molecular weight of the Cardo-based alkali-soluble resin may be 2,000 to 100,000, and preferably 3,000 to 40,000. When the weight average molecular weight is 2,000 to 100,000, adhesion and developability can be improved.

[0384] In one embodiment of the present invention, the content of the Cardo-based alkali-soluble resin may be 1 to 50 parts by weight, preferably 6 to 40 parts by weight, and more preferably 9 to 35 parts by weight, based on 100 parts by weight of the self-luminous photosensitive resin composition.

[0385] When the content of the Cardo-based alkali-soluble resin is within the above range, the solubility in the developer is sufficient and the pattern is easily formed. When the content of the Cardo-based alkali-soluble resin is less than the above range, the non-pixel portion may fall off, and when the content is greater than the above range, the solubility in the developer may decrease and the pattern may be difficult to form.

[0386] In another embodiment of the present invention, the alkali-soluble resin may further include a Cardo-based alkali-soluble resin including one or more repeating units selected from the group consisting of the following Chemical Formula 13 and the following Chemical Formula 14.

[0387]

[0388]

[0389] In the above chemical formulas 13 and 14,

[0390] P is independently

[0391] R13 and R14 are each independently hydrogen, hydroxyl, thiol, amino, nitro or halogen atoms,

[0392] Ar1 is each independently a C6-C15 aryl group,

[0393] Y' is an anhydride residue,

[0394] Z' is an acid dianhydride residue,

[0395] A is O, S, N, Si or Se,

[0396] a and b are each independently an integer of 1 to 6,

[0397] p and q are each independently an integer of 0 to 30,

[0398] Among them, p and q are not 0 at the same time.

[0399] The above-mentioned halogen atom is F, Cl, Br or I.

[0400] The above-mentioned aryl group may be a C6-C15 monocyclic aryl group or a polycyclic aryl group. Examples of the above-mentioned monocyclic aryl group include, but are not limited to, phenyl, biphenyl, terphenyl, stilbene, etc. Examples of the above-mentioned polycyclic aryl group include, but are not limited to, naphthyl, anthracenyl, phenanthrenyl, pyrenyl, peryl, yl, fluorenyl, etc., but are not limited thereto.

[0401] Y' in the above Chemical Formula 13 is a residue of an acid anhydride, and the above contents related to Y can be applied to the acid anhydride that can introduce the residue Y'.

[0402] In the above Chemical Formula 14, Z' is a residue of an acid dianhydride. The acid dianhydride compound into which the residue Z' can be introduced is not particularly limited, and the above contents concerning Z can be applied.

[0403] When the Cardo-based alkali-soluble resin of the present invention is added to the above-mentioned self-luminous photosensitive resin composition, it has the following advantages: by additionally introducing a non-reactive alkali-soluble resin that does not contain unsaturated double bonds, unnecessary photopolymerization caused by reflection of light during the exposure process can be suppressed, and since the solubility in the developer is sufficient due to the adjustment of the acid value based on the content of the resin, pattern formation is easy and residue generation can be suppressed.

[0404] In the case where the alkali-soluble resin further includes a Cardo-based alkali-soluble resin containing one or more repeating units selected from the group consisting of the above Chemical Formula 13 and the above Chemical Formula 14, the content of the Cardo-based alkali-soluble resin may be 1 to 100 parts by weight, preferably 10 to 90 parts by weight, and more preferably 20 to 80 parts by weight, relative to 100 parts by weight of the total alkali-soluble resin.

[0405] When the content of the Cardo-based alkali-soluble resin that may be additionally included is within the above range, the generation of residues in the development step is suppressed, and pattern forming properties are excellent, which is preferred.

[0406] The cardo-based alkali-soluble resin containing at least one repeating unit of the above Chemical Formula 13 and the above Chemical Formula 14 can be produced, for example, by the following method.

[0407] Any of the compounds represented by the following chemical formulas 15 to 19 is reacted with an epoxy compound such as epichlorohydrin in the presence of a base catalyst or an acid catalyst, and then reacted with a compound such as thiophenol, 1-thionaphthalene, or 2-thionaphthalene for synthesis, thereby obtaining the compounds represented by the following chemical formulas 20 to 24.

[0408] Then, the compounds represented by the following Chemical Formulas 20 to 24 are polymerized with carboxylic dianhydride to obtain a Cardo-based alkali-soluble resin containing at least one repeating unit of the above Chemical Formula 13 and the above Chemical Formula 14.

[0409]

[0410]

[0411]

[0412]

[0413]

[0414]

[0415] In the above Chemical Formulas 15 to 19, A, R13 and R14 are the same as defined in the above Chemical Formulas 13 and 14.

[0416]

[0417]

[0418]

[0419]

[0420]

[0421] In the above chemical formulas 20 to 24, c is an integer of 1 to 6,

[0422] A, Ar1, R13 and R14 are the same as defined in Chemical Formulas 13 and 14.

[0423] Specific examples of the carboxylic acid dianhydride include pyromellitic acid dianhydride, 3,3',4,4'-biphenyltetracarboxylic acid dianhydride, 2,3,3',4'-biphenyltetracarboxylic acid dianhydride, 2,2',3,3'-biphenyltetracarboxylic acid dianhydride, 3,3',4,4'-benzophenonetetracarboxylic acid dianhydride, 2,2',3,3'-benzophenonetetracarboxylic acid dianhydride, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, 2,2-bis(2,3-dicarboxyphenyl)propane dianhydride, 1,1-bis(3,4-dicarboxyphenyl)ethane dianhydride, 1,1-bis(2,3-dicarboxyphenyl)ethane dianhydride, bis(3,4-dicarboxyphenyl)methane dianhydride, bis(2,3-dicarboxyphenyl)methane dianhydride, and bis(3,4-dicarboxyphenyl)sulfone. Dianhydride, bis(3,4-dicarboxyphenyl)ether dianhydride, 1,2,5,6-naphthalenetetracarboxylic acid dianhydride, 9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride, 9,9-bis{4-(3,4-dicarboxyphenoxy)phenyl}fluorene dianhydride, 2,3,6,7-naphthalenetetracarboxylic acid dianhydride, 2,3,5,6-pyridinetetracarboxylic acid dianhydride, 3,4,9,10-perylene Aromatic tetracarboxylic dianhydrides such as tetracarboxylic dianhydride and 2,2-bis(3,4-dicarboxyphenyl)hexafluoropropane dianhydride, alicyclic tetracarboxylic dianhydrides such as 1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,2,3,4-cyclopentanetetracarboxylic dianhydride and 1,2,3,4-cyclohexanetetracarboxylic dianhydride, or 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride.

[0424] The polymerization reaction can be carried out, for example, at 100 to 130° C., or 110 to 120° C., for 2 to 24 hours, or 4 to 12 hours.

[0425] The carboxylic dianhydride may be added in an amount of, for example, 5 to 40 parts by weight, 10 to 30 parts by weight, or 10 to 20 parts by weight based on 100 parts by weight of the monomers represented by the chemical formulas 16 to 20.

[0426] The method for producing a cardo-based alkali-soluble resin containing at least one repeating unit of the above Chemical Formula 13 and the above Chemical Formula 14 may include, for example, a step of adding an end-capping agent to carry out a reaction after the above polymerization reaction starts.

[0427] The above-mentioned end-capping reaction can be carried out at, for example, 100 to 130° C., or 110 to 120° C., for 30 minutes to 4 hours, or 1 hour to 3 hours.

[0428] The terminal blocking agent may be added in an amount of, for example, 2 to 10 parts by weight, 2 to 5 parts by weight, or 3 to 5 parts by weight based on 100 parts by weight of the monomers represented by the chemical formulae 20 to 24.

[0429] The terminal blocking agent is preferably, for example, an aromatic carboxylic acid anhydride, and specific examples thereof include phthalic anhydride and the like. In this case, excellent effects of heat resistance, high transmittance, and high refractive index characteristics are achieved.

[0430] The weight average molecular weight of the Cardo-based alkali-soluble resin containing at least one repeating unit of the above Chemical Formula 13 and the above Chemical Formula 14 can be, for example, 1,000 to 100,000 g / mol, preferably 2,000 to 50,000 g / mol, and more preferably 3,000 to 10,000 g / mol. Within this range, the following effects are achieved: excellent heat resistance, suitable development speed of the photosensitive material and development in the developer, easy pattern formation, and high film retention rate.

[0431] The weight average molecular weight can be measured by gel permeation chromatography (GPC).

[0432] The dispersion degree of the Cardo-based alkali-soluble resin containing at least one repeating unit of the above Chemical Formula 13 and the above Chemical Formula 14 can be, for example, in the range of 1.0 to 5.0, and preferably in the range of 1.5 to 4.0. Within this range, it has the following effects: excellent heat resistance, suitable development speed of the photosensitive material and development in the developer, easy pattern formation, and high film retention rate.

[0433] The dispersion degree of the present base material can be measured by the GPC measurement method.

[0434] In another embodiment of the present invention, the alkali-soluble resin may include an acrylic alkali-soluble resin. When the alkali-soluble resin further includes the acrylic alkali-soluble resin, it is advantageous in controlling pattern resolution and adjusting morphology, and thus is preferred.

[0435] Examples of the acrylic alkali-soluble resin include copolymers of a carboxyl group-containing monomer and other monomers copolymerizable with the monomer.

[0436] As the carboxyl group-containing monomer, for example, unsaturated monocarboxylic acids, unsaturated dicarboxylic acids, unsaturated tricarboxylic acids, and other unsaturated carboxylic acids having one or more carboxyl groups in the molecule may be exemplified. Here, as unsaturated monocarboxylic acids, acrylic acid, methacrylic acid, crotonic acid, α-chloroacrylic acid, cinnamic acid, etc. may be exemplified. As unsaturated dicarboxylic acids, maleic acid, fumaric acid, itaconic acid, citraconic acid, mesaconic acid, etc. may be exemplified. The unsaturated polycarboxylic acid may be an acid anhydride, specifically maleic anhydride, itaconic anhydride, citraconic anhydride, etc. may be exemplified. In addition, the unsaturated polycarboxylic acid may also be its mono (2-methacryloyloxyalkyl) ester, succinic acid mono (2-acryloyloxyethyl) ester, succinic acid mono (2-methacryloyloxyethyl) ester, phthalic acid mono (2-acryloyloxyethyl) ester, phthalic acid mono (2-methacryloyloxyethyl) ester, etc. may be exemplified.

[0437] The unsaturated polycarboxylic acid may also be a mono(meth)acrylate of a polymer having dicarboxyl groups at both ends, and examples thereof include ω-carboxyl polycaprolactone monoacrylate, ω-carboxyl polycaprolactone monomethacrylate, etc. These carboxyl-containing monomers may be used alone or in a mixture of two or more. As other monomers capable of copolymerizing with the carboxyl-containing monomers, examples thereof include aromatic vinyl compounds such as styrene, α-methylstyrene, o-vinyltoluene, m-vinyltoluene, p-vinyltoluene, p-chlorostyrene, o-methoxystyrene, m-methoxystyrene, p-methoxystyrene, o-vinylbenzyl methyl ether, m-vinylbenzyl methyl ether, p-vinylbenzyl methyl ether, o-vinylbenzyl glycidyl ether, m-vinylbenzyl glycidyl ether, p-vinylbenzyl glycidyl ether, and indene; methyl acrylate, methyl methacrylate, ethyl acrylate, methyl Ethyl acrylate, n-propyl acrylate, n-propyl methacrylate, isopropyl acrylate, isopropyl methacrylate, n-butyl acrylate, n-butyl methacrylate, isobutyl acrylate, isobutyl methacrylate, sec-butyl acrylate, sec-butyl methacrylate, tert-butyl acrylate, tert-butyl methacrylate, 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl acrylate, 2-hydroxypropyl methacrylate, 3-hydroxypropyl acrylate, 3-hydroxypropyl methacrylate, 2-hydroxybutyl acrylate, 2-hydroxybutyl methacrylate , 3-hydroxybutyl acrylate, 3-hydroxybutyl methacrylate, 4-hydroxybutyl acrylate, 4-hydroxybutyl methacrylate, allyl acrylate, allyl methacrylate, benzyl acrylate, benzyl methacrylate, cyclohexyl acrylate, cyclohexyl methacrylate, phenyl acrylate, phenyl methacrylate, 2-methoxyethyl acrylate, 2-methoxyethyl methacrylate, 2-phenoxyethyl acrylate, 2-phenoxyethyl methacrylate, methoxydiethylene glycol acrylate, methoxydiethylene glycol methacrylate, methoxytriethylene glycol acrylate unsaturated carboxylic acid esters such as esters of methoxytriethylene glycol methacrylate, methoxypropylene glycol acrylate, methoxypropylene glycol methacrylate, methoxydipropylene glycol acrylate, methoxydipropylene glycol methacrylate, isobornyl acrylate, isobornyl methacrylate, dicyclopentadienyl acrylate, dicyclopentadienyl methacrylate, adamantyl (meth)acrylate, norbornyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl acrylate, 2-hydroxy-3-phenoxypropyl methacrylate, glyceryl monoacrylate, glyceryl monomethacrylate, etc.;Unsaturated carboxylic acid aminoalkyl esters such as 2-aminoethyl acrylate, 2-aminoethyl methacrylate, 2-dimethylaminoethyl acrylate, 2-dimethylaminoethyl methacrylate, 2-aminopropyl acrylate, 2-aminopropyl methacrylate, 2-dimethylaminopropyl acrylate, 2-dimethylaminopropyl methacrylate, 3-aminopropyl acrylate, 3-aminopropyl methacrylate, 3-dimethylaminopropyl acrylate, 3-dimethylaminopropyl methacrylate; unsaturated carboxylic acid glycidyl esters such as glycidyl acrylate and glycidyl methacrylate; carboxylic acid vinyl esters such as vinyl acetate, vinyl propionate, vinyl butyrate, and vinyl benzoate; vinyl methyl ether, vinyl ethyl ether, allyl glycidyl acrylate, Unsaturated ethers such as glyceryl ether; cyanide vinyl compounds such as acrylonitrile, methacrylonitrile, α-chloroacrylonitrile, and vinylene cyanide; unsaturated amides such as acrylamide, methacrylamide, α-chloroacrylamide, N-2-hydroxyethylacrylamide, and N-2-hydroxyethylmethacrylamide; unsaturated imides such as maleimide, benzylmaleimide, N-phenylmaleimide, and N-cyclohexylmaleimide; aliphatic conjugated dienes such as 1,3-butadiene, isoprene, and chloroprene; and macromonomers having a monoacryloyl group or a monomethacryloyl group at the end of the polymer molecular chain of polystyrene, polymethyl acrylate, polymethyl methacrylate, polybutyl acrylate, polybutyl methacrylate, and polysiloxane. These monomers can be used alone or in combination of two or more. ;

[0438] In particular, bulky monomers such as monomers having a norbornane skeleton, monomers having an adamantane skeleton, and monomers having a rosin skeleton are preferred as other monomers copolymerizable with the carboxyl group-containing monomer because they tend to reduce the relative dielectric constant value.

[0439] The content of the acrylic alkali-soluble resin can be, for example, 1 to 50 parts by weight, preferably 3 to 40 parts by weight, and more preferably 5 to 30 parts by weight relative to 100 parts by weight of the alkali-soluble resin as a whole. In this case, it has the advantages of sufficient solubility in the developer and it is not easy for non-pixel parts to produce residues on the substrate, making it easy to adjust the resolution and shape of the pattern.

[0440] The content of the alkali-soluble resin is usually 5 to 85 parts by weight, preferably 10 to 70 parts by weight, relative to 100 parts by weight of the total solid content in the self-luminous photosensitive resin composition. When the content of the alkali-soluble resin satisfies the above range, it has sufficient solubility in the developer and is unlikely to produce development residues on the substrate in the non-pixel part, and it is unlikely to reduce the film of the pixel part of the exposed part during development, and the non-pixel part has a good tendency to fall off, so it is preferred.

[0441] <Light Conversion Laminated Substrate>

[0442] The light conversion laminate substrate of the present invention comprises a cured product of a quantum dot light conversion composition. The light conversion laminate substrate comprises a quantum dot light conversion composition that can be applied to a glass substrate, thereby enabling the use of a solvent that is not harmful to human health, thereby improving operator safety and product productivity.

[0443] The light conversion layer substrate may be silicon (Si), silicon oxide (SiOx) or a polymer substrate. The polymer substrate may be polyethersulfone (PES) or polycarbonate (PC).

[0444] The light conversion laminate substrate may be formed by applying the quantum dot light conversion composition and thermally curing the composition.

[0445] <Quantum Dot Light Emitting Diodes>

[0446] A quantum dot light-emitting diode (QLED) according to an embodiment of the present invention may include the aforementioned quantum dots.

[0447] The quantum dot light-emitting diode is an electroluminescence (EL) device in which quantum dots are electrically excited to emit light.

[0448] In the case of the quantum dot light-emitting diode, the electrons and holes injected from the electrodes on both sides form excitons in the quantum dot light-emitting layer, and light is emitted through the radiative recombination of the excitons. Since the working principle is the same as that of the organic light-emitting diode (OLED), it can be constructed by directly using the multi-layer element structure of the electron / hole injection layer and the transport layer of the conventional OLED, and only replacing the organic light-emitting element with quantum dots in the light-emitting layer.

[0449] The method for producing the quantum dot light-emitting diode of the present invention is not particularly limited, and a method known in the technical field can be used.

[0450] In one embodiment, the method for manufacturing a quantum dot light-emitting diode can be manufactured by sequentially stacking an anode, a cathode, an electron injection / transport layer, a light-emitting layer, a hole transport layer, and a hole injection layer.

[0451] In another embodiment, the method for manufacturing a quantum dot light-emitting diode can also be manufactured by sequentially stacking a cathode, an electron injection / transport layer, a light-emitting layer, a hole transport layer, a hole injection layer and an anode. In yet another embodiment, the method for manufacturing a quantum dot light-emitting diode can also be manufactured by sequentially stacking an anode, a hole injection layer, a hole transport layer, an electron blocking layer, a light-emitting layer, an electron injection / transport layer and a cathode.

[0452] In this case, the light-emitting layer may include the quantum dots.

[0453] <Quantum dot film>

[0454] The quantum dot film according to an embodiment of the present invention may include the above-mentioned quantum dots.

[0455] The quantum dot film includes a quantum dot dispersion layer containing a polymer resin and the quantum dots dispersed in the polymer resin.

[0456] As the above-mentioned polymer resin, for example, epoxy resin, epoxy acrylate, lauryl acrylate, norbornene, polyethylene, polystyrene, ethylene-styrene copolymer, acrylate containing bisphenol A and bisphenol A derivatives, acrylate containing fluorene derivatives, isobornyl acrylate, polyphenylalkylsiloxane, polydiphenylsiloxane, polydialkylsiloxane, silsesquioxane, fluorinated silicone, and vinyl and hydride substituted silicone, etc. can be used. These polymer resins can be used alone or in combination of two or more.

[0457] The quantum dot film may further include a barrier layer on at least one surface of the quantum dot dispersed layer.

[0458] The barrier layer may have a thickness of 0.001 cm 3 / m 2 ·Day·Bar(cm 3 / m 2 ·day·bar) and an oxygen permeability of less than 0.001g / m 2 · Water permeability of less than 10 days, such as polyester, polycarbonate, polyolefin, cyclic olefin polymer or polyimide.

[0459] The thickness of the quantum dot scattered layer may be 10 μm to 100 μm, and the thickness of the barrier layer may be 50 μm to 70 μm.

[0460] The method for producing the quantum dot film of the present invention is not particularly limited, and a method known in the technical field can be used.

[0461] In one embodiment, the method for manufacturing a quantum dot film may include:

[0462] a) preparing a lower transparent substrate;

[0463] b) coating the quantum dot dispersion on the lower transparent substrate to form a quantum dot film; and

[0464] c) A step of laminating an upper transparent substrate on the quantum dot thin film to produce a quantum dot film.

[0465] <Color Filter>

[0466] The color filter of the present invention is formed using the self-luminous photosensitive resin composition described above.

[0467] The pattern forming method for forming the color filter of the present invention can be a method known in the art.

[0468] In one embodiment, the pattern forming method may include:

[0469] a) applying the self-luminous photosensitive resin composition to a substrate;

[0470] b) a pre-baking step to dry the solvent;

[0471] c) irradiating the obtained film with active light through a photomask to cure the exposed portion;

[0472] d) performing a developing step of dissolving the unexposed portion with an alkaline aqueous solution; and

[0473] e) performing drying and post-baking steps.

[0474] The substrate may be a glass substrate or a polymer substrate, but is not limited thereto. As the glass substrate, it is particularly preferred to use soda-lime glass, glass containing barium or strontium, lead glass, aluminosilicate glass, borosilicate glass, barium borosilicate glass or quartz. In addition, as the polymer substrate, polycarbonate, acrylic, polyethylene terephthalate, polyether sulfide or polysulfone substrates may be cited.

[0475] At this time, coating can be performed by a known wet coating method using a coating device such as a roll coater, a spin coater, a slot spin coater, a slot coater (sometimes also referred to as a die coater), or an inkjet machine so as to obtain a desired thickness.

[0476] Pre-baking is performed by heating in an oven, a hot plate, etc. The heating temperature and heating time during pre-baking are appropriately selected according to the solvent used, and for example, the pre-baking can be performed at a temperature of 80 to 150° C. for 1 to 30 minutes.

[0477] The exposure after pre-baking is performed by using an exposure machine, and the exposure is performed through a photomask so that only the portion corresponding to the pattern is exposed to light. At this time, the light used for irradiation can be, for example, visible light, ultraviolet light, X-rays, electron beams, etc.

[0478] The developing step of dissolving the unexposed part with an alkaline aqueous solution after exposure is performed for the purpose of removing the unremoved part of the photosensitive resin composition of the unexposed part, and the desired pattern is formed by the development. As a developer suitable for the development with the alkaline aqueous solution, for example, an aqueous solution of a carbonate of an alkali metal or an alkaline earth metal can be used. In particular, the alkaline aqueous solution containing 1 to 3% by weight of a carbonate such as sodium carbonate, potassium carbonate, lithium carbonate, etc. can be used at a temperature of 10 to 50°C, preferably 20 to 40°C, using a developing machine or an ultrasonic cleaning agent.

[0479] Post-baking is performed to improve the adhesion between the patterned film and the substrate, and can be achieved by, for example, heat treatment at 80 to 250° C. for 10 to 120 minutes. Post-baking can be performed using an oven, a hot plate, or the like, similar to pre-baking.

[0480] <Image Display Device>

[0481] The image display device of the present invention comprises the color filter or the light conversion laminate substrate. The image display device specifically includes a liquid crystal display (liquid crystal display device; LCD), an organic EL display (organic EL display device), a liquid crystal projector, a display device for a game console, a display device for a portable terminal such as a portable phone, a display device for a digital camera, a display device for a car navigation system, and the like, and is particularly suitable for a color display device.

[0482] The image display device may include, in addition to the color filter or light conversion stack substrate, a configuration known in the art in the technical field of the present invention. That is, the present invention includes an image display device to which the color filter or light conversion stack substrate can be applied.

[0483] An image display device including the color filter of the present invention can have excellent characteristics in terms of color reproducibility, brightness, light resistance, reliability, and the like.

[0484] Hereinafter, the present invention will be described in more detail by way of examples. However, the following examples are provided to more specifically describe the present invention, and the scope of the present invention is not limited to the following examples.

[0485] Synthesis Example 1: InP / ZnS Core-Shell Quantum Dot Synthesis

[0486] 0.05839 g of indium acetate, 0.12019 g of oleic acid and 10 mL of 1-octadecene (ODE) were added to a three-necked flask, and the flask was degassed at 110° C. and 100 mTorr for 30 minutes while being stirred, and then heated to 270° C. under an inert gas until the solution became transparent.

[0487] As a phosphorus (P) precursor, prepare 0.025054g of tri(trimethylsilyl)phosphine, add 0.5mL of 1-octadecene and 0.5mL of tri-n-octylphosphine, and quickly inject it into the above-mentioned flask heated to 270°C under inert gas while stirring. After reacting for 1 hour, the reaction is terminated by rapid cooling. Then, when the temperature of the flask reaches 100°C, inject 10mL of toluene and move it to a 50mL centrifuge tube. After adding 10mL of ethanol, refine it twice by precipitation and redispersion method. The refined InP core nanoparticles are dispersed in 1-octadecene and stored.

[0488] 3.669 g of zinc acetate, 20 mL of oleic acid and 20 mL of 1-octadecene were added to a three-necked flask, and the mixture was degassed at 110° C. and 100 mTorr for 30 minutes while being stirred. The mixture was then heated to 270° C. under an inert gas until the solution became transparent, and then cooled to 60° C. to obtain a transparent precursor solution in the form of zinc oleate.

[0489] 0.6412 g of sulfur and 10 mL of tri-n-octylphosphine were added to a three-necked flask, and the mixture was stirred in an inert gas atmosphere until the solution became transparent. The mixture was heated to 80° C. and then cooled to room temperature to obtain a S precursor solution in the form of TOP:S.

[0490] Add the prepared InP core nanoparticle solution to another three-necked flask, adjust the temperature of the flask to 300°C, and quickly inject 0.6mL of the prepared zinc precursor solution using a syringe. Then, use a syringe pump to inject 0.3mL of the prepared S precursor solution into the flask at a rate of 2mL / hr. After the injection, the reaction is further carried out for 3 hours, and then the reaction is terminated by rapid cooling. When the temperature of the flask reaches 100°C, inject 10mL of toluene and move it to a 50mL centrifuge tube. After adding 10mL of ethanol, it is refined twice by precipitation and redispersion method. The refined InP / ZnS core-shell structure nanoparticles are dispersed in normal chloroform and stored. The solid content is adjusted to 10%. The maximum emission wavelength is 525nm.

[0491] Synthesis Example 2: InP / ZnSe / ZnS Core-Shell Quantum Dot Synthesis

[0492] Indium acetate 0.4mmol (0.058g), palmitic acid 0.6mmol (0.15g) and 1-octadecene 20mL were added to the reactor and heated to 120°C under vacuum. After 1 hour, the atmosphere in the reactor was switched to nitrogen. After heating to 280°C, a mixed solution of tri(trimethylsilyl)phosphine (TMS3P) 0.2mmol (58μl) and trioctylphosphine 1.0mL was quickly injected and reacted for 0.5 minutes.

[0493] Next, 2.4mmoL (0.448g) of zinc acetate, 4.8mmol of oleic acid and 20mL of trioctylamine were added to the reactor and heated to 120°C under vacuum. After 1 hour, the atmosphere in the reactor was converted to nitrogen and the reactor was heated to 280°C. 2mL of the previously synthesized InP core solution was added, followed by 4.8mmol of selenium (Se / TOP) in trioctylphosphine, and the final mixture was reacted for 2 hours. Ethanol was added to the reaction solution that was rapidly cooled to room temperature, centrifuged, and the resulting precipitate was filtered under reduced pressure, and then dried under reduced pressure to form an InP / ZnSe core-shell.

[0494] Next, 2.4mmol (0.448g) of zinc acetate, 4.8mmol of oleic acid and 20mL of trioctylamine were added to the reactor and heated to 120°C under vacuum. After 1 hour, the atmosphere in the reactor was converted to nitrogen and the reactor was heated to 280°C. 2mL of the previously synthesized InP core solution was added, followed by 4.8mmol of sulfur (S / TOP) in trioctylphosphine, and the final mixture was reacted for 2 hours. Ethanol was added to the reaction solution that was rapidly cooled to room temperature, centrifuged, and the resulting precipitate was filtered under reduced pressure, then dried under reduced pressure to obtain quantum dots of InP / ZnSe / ZnS core-shell structure, which were then dispersed in chloroform. The solid content was adjusted to 10%. The maximum emission wavelength was 520nm.

[0495] Synthesis Example 3: Cardo Alkali-Soluble Resin (BP-1)

[0496] (1) 138 g of 9,9'-bis(4-glycyloxyphenyl)fluorene (Hearchem) as a bisphenol epoxy compound, 54 g of 2-carboxyethyl acrylate, 1.4 g of benzyltriethylammonium chloride (Oi Kakin Co., Ltd.), 1 g of triphenylphosphine (Aldrich Co., Ltd.), 128 g of propylene glycol methyl ethyl acetate (Daicel Chemical Co., Ltd.) and 0.5 g of hydroquinone were added to a reactor, and the temperature was raised to 120°C and maintained for 12 hours to synthesize a compound represented by the following chemical formula 25.

[0497] (2) 60 g of the compound represented by the following chemical formula 25, 11 g of biphenyltetracarboxylic dianhydride (Mitsubishi Gas), 3 g of tetrahydrophthalic anhydride (Aldrich), 20 g of propylene glycol methyl ethyl acetate (Daicel Chemical Co., Ltd.), and 0.1 g of N,N'-tetramethylammonium chloride were added to a reactor, and the temperature was raised to 120°C and maintained for 2 hours to synthesize the compound represented by the following [chemical formula 26]. The weight average molecular weight of the obtained resin represented by [chemical formula 26] was 5,400 g / mol.

[0498]

[0499]

[0500] Synthesis Example 4: Cardo Alkali-Soluble Resin (BP-2)

[0501] (1) In order to synthesize the compound of Chemical Formula 27, 3',6'-dihydroxyspiro(fluorene-9,9-xanthene) 364.4 g and 0.4159 g of tert-butylammonium bromide were mixed in a 3000 ml three-necked round-bottom flask, 2359 g of epichlorohydrin was added, and the mixture was heated to 90° C. for reaction. When the 3,6-dihydroxyspiro(fluorene-9,9-xanthene) completely disappeared, the mixture was cooled to 30° C. and a 50% aqueous solution of NaOH (3 equivalents) was slowly added. When the epichlorohydrin completely disappeared, the mixture was extracted with dichloromethane, washed with water three times, and then the organic layer was dried with magnesium sulfate. Then, the dichloromethane was distilled under reduced pressure and recrystallized using dichloromethane and methanol in a mixing ratio of 50:50.

[0502] After mixing 1 equivalent of the epoxy compound synthesized in this way with 0.004 equivalent of tert-butylammonium bromide, 0.001 equivalent of 2,6-diisobutylphenol, and 2.2 equivalents of acrylic acid, 24.89 g of propylene glycol monomethyl ether acetate solvent is added and mixed. In the reaction solution, the temperature is heated to 90-100°C while blowing air at 25 ml / min to dissolve. For the reaction solution, the temperature is raised to 120°C from the turbid state to completely dissolve it. If the solution becomes transparent and the viscosity increases, the acid value is measured and stirred until the acid value is less than 1.0 mgKOH / g. It takes 11 hours for the acid value to reach the target (0.8). After the reaction is completed, the temperature of the reactor is lowered to room temperature to obtain a colorless and transparent compound.

[0503]

[0504] (2) After adding 600 g of propylene glycol monomethyl ether acetate to 307.0 g of the compound of Chemical Formula 27 and dissolving it, 78 g of biphenyltetracarboxylic dianhydride and 1 g of tetraethylammonium bromide were mixed, and the temperature was slowly raised to react at 110-115° C. for 4 hours. After confirming the disappearance of the anhydride group, 38.0 g of 1,2,3,6-tetrahydrophthalic anhydride was mixed and reacted at 90° C. for 6 hours to polymerize into a Cardo-based alkali-soluble resin. The disappearance of the anhydride was confirmed by IR spectroscopy.

[0505] Synthesis Example 5: Cardo Alkali-Soluble Resin (BP-3)

[0506] (1) After installing a reflux condenser and a thermometer in a three-necked flask, add 42.5 g of 9,9-bisphenolfluorene and quantitatively inject 220 mL of 2-(chloromethyl)oxirane. After adding 100 mg of tetrabutylammonium bromide, start stirring and raise the temperature to 90°C. After confirming that the content of unreacted products is less than 0.3%, perform vacuum distillation.

[0507] After the temperature is lowered to 30°C, dichloromethane is injected and NaOH is slowly added. After confirming that the product is 96% or more by high performance liquid chromatography (HPLC), 5% HCl is added dropwise to terminate the reaction. After extracting the reactants and separating the layers, the organic layer is washed with water until it becomes neutral. After drying the organic layer with MgSO4, it is concentrated by vacuum distillation using a rotary evaporator. Dichloromethane is added to the concentrated product, the temperature is raised to 40°C, methanol is added while stirring, and then the solution temperature is lowered and stirred. After filtering the generated solid, vacuum drying is performed at room temperature to obtain 52.7g (yield 94%) of white solid powder, whose structure is confirmed by 1HNMR.

[0508]

[0509] 1H NMR in CDCl3: 7.75(2H),7.35-7.254(6H),7.08(4H),6.74(4H),4.13(2H),3.89(2H),3.30(2H),2.87(2H),2.71(2H).

[0510] (2) An example of synthesizing Chemical Formula 20, 3,3′-(((9H-fluorene-9,9-diyl)bis(4,1-phenylene))bis(oxy))bis(1-phenylthio)propan-2-ol) (3,3′-(((9H-fluorene-9,9-diyl)bis(4,1-phenylene))bis(oxy))bis(1-(phenylthio)propan-2-ol)).

[0511] After setting a reflux condenser and a thermometer in a three-necked flask, add the reactant (1000 g) of step (1), 524 g of thiophenol, and 617 g of ethanol and stir. Slowly drop 328 g of triethylamine into the reaction solution. After confirming the disappearance of the initial substance by high performance liquid chromatography (HPLC), terminate the reaction. After the reaction is completed, remove the ethanol by vacuum distillation. After dissolving the organic matter in dichloromethane, wash with water, and then remove the dichloromethane by vacuum distillation. After dissolving the concentrated organic matter in ethyl acetate, add ether solvent and stir for 30 minutes. The compound is vacuum distilled to obtain 945 g of pale yellow oil (yield 64%), and its structure is confirmed by 1H NMR.

[0512]

[0513] 1H NMR in CDCl3: 7.82(2H),7.38-6.72(20H),6.51(4H),4.00(2H),3.97(2H),3.89(2H),3.20(2H),3.01(2H),2.64(2H).

[0514] (3) Synthesis of alkali-soluble resin

[0515] After installing a reflux condenser and a thermometer in a three-necked flask, 200 g of the 3,3'-(((9H-fluorene-9,9-diyl)bis(4,1-phenylene))bis(oxy))bis(1-phenylthio)propan-2-ol) monomer synthesized in step (2) dissolved in 50% PGMEA solvent was added, and the temperature was raised to 115° C. 3,3,'4,4'-biphenyltetracarboxylic dianhydride (31.1 g) was added dropwise at 115° C., and the mixture was stirred while maintaining the temperature at 115° C. for 6 hours. After adding 7.35 g of phthalic anhydride and stirring for further 2 hours, the reaction was terminated and cooled to obtain an alkali-soluble resin having a weight average molecular weight of 3,500 g / mol.

[0516] Synthesis Example 6: Acrylic alkali-soluble resin (BP-4)

[0517] A flask equipped with a stirrer, a thermometer, a reflux condenser, a dropping funnel, and a nitrogen inlet tube was prepared. On the other hand, 45 parts by weight of N-benzylmaleimide, 45 parts by weight of methacrylic acid, 10 parts by weight of tricyclodecyl methacrylate, 4 parts by weight of tert-butyl peroxy-2-ethylhexanoate, and 40 parts by weight of propylene glycol monomethyl ether acetate (hereinafter, PGMEA) were added and stirred and mixed to prepare a monomer dropping funnel, and 6 parts by weight of n-dodecyl mercaptan and 24 parts by weight of PGMEA were added and stirred and mixed to prepare a chain transfer agent dropping funnel. After that, 395 parts by weight of PGMEA was introduced into the flask, and after the atmosphere in the flask was changed from air to nitrogen, the temperature of the flask was raised to 90°C while stirring. Then, the monomer and chain transfer agent were added dropwise from the dropping funnel. When dropping, the temperature was maintained at 90°C for 2 hours, and after 1 hour, the temperature was raised to 110°C and maintained for 3 hours, and then a gas inlet tube was introduced to start bubbling of a mixed gas of oxygen / nitrogen = 5 / 95 (v / v). Next, 10 parts by weight of glycidyl methacrylate, 0.4 parts by weight of 2,2'-methylenebis(4-methyl-6-tert-butylphenol), and 0.8 parts by weight of triethylamine were added to the flask, and the reaction was continued at 110°C for 8 hours. After that, the reaction was cooled to room temperature, and an alkali-soluble resin having a solid content of 29.1% by weight, a weight average molecular weight of 32,000, and an acid value of 114 mgKOH / g was obtained.

[0518] Examples 1 to 28 and Comparative Examples 1 to 8: Preparation of Quantum Dots

[0519] Example 1: Ligand Substitution Reaction 1 (LE-1)

[0520] 5 mL of the quantum dot solution obtained in Synthesis Example 1 was placed in a centrifuge tube, and 20 mL of ethanol was added to precipitate it. The supernatant was removed by centrifugation, 3 mL of chloroform was added to the precipitate to disperse the quantum dots, and 2.50 g of Bis[2-(methacryloyloxy)ethyl]phosphate (TCI) represented by the following chemical formula 1-1 was added, and the mixture was heated to 60°C and reacted for one hour under a nitrogen atmosphere.

[0521]

[0522] Next, 25 mL of n-hexane was added to the reaction product to precipitate the quantum dots, and then centrifuged. After the precipitate was separated, 4 mL of propylene glycol monomethyl ether acetate was added and dispersed while heating to 80° C. The solid content was adjusted to 10% using PGMEA. The maximum emission wavelength was 516 nm.

[0523] Example 2: Ligand Substitution Reaction 2 (LE-2)

[0524] The same procedure as in Example 1 was carried out except that bis[2-(methacryloyloxy)hexyl]phosphate (TCI Corporation) represented by the following chemical formula 1-2 was used instead of the ligand used in Example 1.

[0525]

[0526] The solid content was adjusted to 10% with PGMEA. The maximum emission wavelength was 516 nm.

[0527] Example 3: Ligand Substitution Reaction 3 (LE-3)

[0528] 5 mL of the quantum dot solution obtained in Synthesis Example 2 was placed in a centrifuge tube, and 20 mL of ethanol was added to precipitate it. The supernatant was removed by centrifugation, 3 mL of chloroform was added to the precipitate to disperse the quantum dots, and 3.00 g of bis[2-(methacryloyloxy)ethyl]phosphate (TCI Company) represented by the above chemical formula 1-1 was added, and the mixture was reacted for one hour while heating to 60° C. under a nitrogen atmosphere.

[0529] Next, 25 mL of n-hexane was added to the reaction product to precipitate the quantum dots, and then centrifuged. After the precipitate was separated, 4 mL of propylene glycol monomethyl ether acetate was added and dispersed while heating to 80° C. The solid content was adjusted to 10% using PGMEA. The maximum emission wavelength was 516 nm.

[0530] Example 4: Ligand Substitution Reaction 4 (LE-4)

[0531] The same procedure as in Example 3 was carried out except that bis[2-(methacryloyloxy)hexyl]phosphate (TCI Corporation) represented by the above Chemical Formula 1-2 was used instead of the ligand used in Example 3.

[0532] The solid content was adjusted to 10% with PGMEA. The maximum emission wavelength was 516 nm.

[0533] Example 5: Ligand Substitution Reaction 5 (LE-5)

[0534] The same procedure as in Example 3 was carried out except that the compound represented by the following Chemical Formula 1-3 was used instead of the ligand used in Example 3.

[0535]

[0536] The solid content was adjusted to 10% with PGMEA. The maximum emission wavelength was 518 nm.

[0537] Example 6: Ligand Substitution Reaction 6 (LE-6)

[0538] The same procedure as in Example 3 was carried out except that the compound represented by the following Chemical Formula 1-4 was used instead of the ligand used in Example 3.

[0539]

[0540]

[0541] The solid content was adjusted to 10% with PGMEA. The maximum emission wavelength was 515 nm.

[0542] Example 7: Ligand Substitution Reaction 7 (LE-7)

[0543] The same procedure as in Example 3 was carried out except that the compound represented by the following Chemical Formula 1-5 was used instead of the ligand used in Example 3.

[0544]

[0545] The solid content was adjusted to 10% with PGMEA. The maximum emission wavelength was 517 nm.

[0546] Example 8: Ligand Substitution Reaction 8 (LE-8)

[0547] The same procedure as in Example 3 was carried out except that the compound represented by the following Chemical Formula 1-6 was used instead of the ligand used in Example 3.

[0548]

[0549] The solid content was adjusted to 10% with PGMEA. The maximum emission wavelength was 518 nm.

[0550] Example 9: Ligand Substitution Reaction 9 (LE-9)

[0551] The same procedure as in Example 3 was carried out except that the compound represented by the following Chemical Formula 1-7 was used instead of the ligand used in Example 3.

[0552]

[0553] The solid content was adjusted to 10% with PGMEA. The maximum emission wavelength was 516 nm.

[0554] Example 10: Ligand Substitution Reaction 10 (LE-10)

[0555] 5 mL of the quantum dot solution obtained in Synthesis Example 1 was placed in a centrifuge tube, and 20 mL of ethanol was added to precipitate it. The supernatant was removed by centrifugation, and 3 mL of chloroform was added to the precipitate to disperse the quantum dots. Then, 1.00 g of 2-carboxyethyl acrylate (2-Carboxyethyl acrylate (Aldrich)) represented by the following chemical formula 2-1 was added, and the mixture was reacted for one hour while being heated to 60° C. under a nitrogen atmosphere.

[0556]

[0557] Next, 25 mL of n-hexane was added to the reaction product to precipitate the quantum dots, and then centrifugation was performed. After the precipitate was separated, propylene glycol monomethyl ether acetate (PGMEA) was added and dispersed so that the solid content became 10%. The maximum emission wavelength was 520 nm.

[0558] Example 11: Ligand Substitution Reaction 11 (LE-11)

[0559] 5 mL of the quantum dot solution obtained in Synthesis Example 1 was placed in a centrifuge tube, and 20 mL of ethanol was added to precipitate it. The supernatant was removed by centrifugation, and 3 mL of chloroform was added to the precipitate to disperse the quantum dots. Then, 1.00 g of 2-carboxypropyl methacrylate (Alfachemistry) represented by the following chemical formula 2-2 was added, and the mixture was reacted for one hour while being heated to 60° C. under a nitrogen atmosphere.

[0560]

[0561] Next, 25 mL of n-hexane was added to the reaction product to precipitate the quantum dots, and then centrifugation was performed. After the precipitate was separated, propylene glycol monomethyl ether acetate (PGMEA) was added and dispersed so that the solid content became 10%. The maximum emission wavelength was 520 nm.

[0562] Example 12: Ligand Substitution Reaction 12 (LE-12)

[0563] 5 mL of the quantum dot solution obtained in Synthesis Example 2 was placed in a centrifuge tube, and 20 mL of ethanol was added to precipitate it. The supernatant was removed by centrifugation, 3 mL of chloroform was added to the precipitate to disperse the quantum dots, and 1.00 g of 4-(acryloyloxy)benzoic acid (Angenechemical Co., Ltd.) represented by the following chemical formula 2-3 was added, and the mixture was reacted for one hour while being heated to 60° C. under a nitrogen atmosphere.

[0564]

[0565] Next, 25 mL of n-hexane was added to the reaction product to precipitate the quantum dots, and then centrifugation was performed. After the precipitate was separated, propylene glycol monomethyl ether acetate (PGMEA) was added and dispersed so that the solid content became 10%. The maximum emission wavelength was 521 nm.

[0566] Example 13: Ligand Substitution Reaction 13 (LE-13)

[0567] 5 mL of the quantum dot solution obtained in Synthesis Example 2 was placed in a centrifuge tube, and 20 mL of ethanol was added to precipitate it. The supernatant was removed by centrifugation, 3 mL of chloroform was added to the precipitate to disperse the quantum dots, and 1.00 g of 6-acryloyloxy-2-naphthoic acid (Angene Chemical Co., Ltd.) represented by the following chemical formula 2-4 was added, and the mixture was heated to 60° C. and reacted for one hour under a nitrogen atmosphere.

[0568]

[0569] Next, 25 mL of n-hexane was added to the reaction product to precipitate the quantum dots, and then centrifugation was performed. After the precipitate was separated, propylene glycol monomethyl ether acetate (PGMEA) was added and dispersed so that the solid content became 10%. The maximum emission wavelength was 522 nm.

[0570] Example 14: Ligand Substitution Reaction 14 (LE-14)

[0571] The same procedure as in Example 10 was carried out except that mono-2-(Acryloyloxy)ethyl succinate (Aldrich) represented by the following Chemical Formula 3-1 was used instead of the ligand used in Example 10.

[0572]

[0573] The solid content was adjusted to 10% using propylene glycol monomethyl ether acetate (PGMEA). The maximum emission wavelength was 520 nm.

[0574] Example 15: Ligand Substitution Reaction 15 (LE-15)

[0575] The same procedure as in Example 10 was carried out except that 4-[2-(Methacryloyloxy)ethoxy]-4-oxobutanoic acid (Abclabtory Scientific) represented by the following Chemical Formula 3-2 was used instead of the ligand used in Example 10.

[0576]

[0577] The solid content was adjusted to 10% using propylene glycol monomethyl ether acetate (PGMEA). The maximum emission wavelength was 520 nm.

[0578] Example 16: Ligand Substitution Reaction 16 (LE-16)

[0579] The same procedure as in Example 12 was carried out except that 2-acryloyloxyethyl hexahydro phthalate (KYOEISHA CHEMICAL CO., LTD.) represented by the following Chemical Formula 3-3 was used instead of the ligand used in Example 12.

[0580]

[0581] The solid content was adjusted to 10% using propylene glycol monomethyl ether acetate (PGMEA). The maximum emission wavelength was 520 nm.

[0582] Example 17: Ligand Substitution Reaction 17 (LE-17)

[0583] The same procedure as in Example 12 was carried out except that mono-2-(methacryloyloxy)ethyl phthalate (TCI Corporation) represented by the following Chemical Formula 3-4 was used instead of the ligand used in Example 12.

[0584]

[0585] The solid content was adjusted to 10% using propylene glycol monomethyl ether acetate (PGMEA). The maximum emission wavelength was 520 nm.

[0586] Example 18: Ligand Substitution Reaction 18 (LE-18)

[0587] The same procedure as in Example 12 was carried out except that mono-2-(methacryloyloxy)ethyl maleate (Sigma Aldrich) represented by the following Chemical Formula 3-5 was used instead of the ligand used in Example 12.

[0588]

[0589] The solid content was adjusted to 10% using propylene glycol monomethyl ether acetate (PGMEA). The maximum emission wavelength was 521 nm.

[0590] Example 19: Ligand Substitution Reaction 19 (LE-19)

[0591] 5 mL of the quantum dot solution obtained in Synthesis Example 1 was placed in a centrifuge tube, and 20 mL of ethanol was added to precipitate it. The supernatant was removed by centrifugation, and 3 mL of chloroform was added to the precipitate to disperse the quantum dots. Then, 0.5 g of 2-carboxyethyl acrylate (Aldrich) represented by the above chemical formula 2-1 and 0.5 g of mono-2-(acryloyloxy)ethyl succinate (Aldrich) represented by the above chemical formula 3-1 were added, and the mixture was reacted for one hour while heating to 60°C under a nitrogen atmosphere. 25 mL of n-hexane was added to the reactant to precipitate the quantum dots, and then centrifuged. After separating the precipitate, propylene glycol monomethyl ether acetate (PGMEA) was added and dispersed in such a way that the solid content became 10%. The maximum emission wavelength is 520 nm.

[0592] Example 20: Ligand Substitution Reaction 20 (LE-20)

[0593] 5 mL of the quantum dot solution obtained in Synthesis Example 1 was placed in a centrifuge tube, and 20 mL of ethanol was added to precipitate it. The supernatant was removed by centrifugation, and 3 mL of chloroform was added to the precipitate to disperse the quantum dots. Then, 1.0 g of AC-PEG-SH, 2K (MW = 2K, Biochempeg Scientific) represented by the following chemical formula 4-1 was added, and the mixture was heated to 60°C and reacted for one hour under a nitrogen atmosphere.

[0594]

[0595] Next, 25 mL of n-hexane was added to the reaction product to precipitate the quantum dots, and then centrifugation was performed. After the precipitate was separated, propylene glycol monomethyl ether acetate (PGMEA) was added and dispersed so that the solid content became 10%. The maximum emission wavelength was 520 nm.

[0596] Example 21: Ligand Substitution Reaction 21 (LE-21)

[0597] The same procedure as in Example 20 was carried out except that 1.0 g of AC-PEG-SH,5K (MW=5K, Biochemeg Scientific) represented by the above Chemical Formula 4-1 was used instead of the ligand used in Example 20.

[0598] The solid content was adjusted to 10% using propylene glycol monomethyl ether acetate (PGMEA). The maximum emission wavelength was 520 nm.

[0599] Example 22: Ligand Substitution Reaction 22 (LE-22)

[0600] The same procedure as in Example 20 was carried out except that 1.0 g of AC-PEG-SH, 10K (MW=10K, Biochemeg Scientific) represented by the above Chemical Formula 4-1 was used instead of the ligand used in Example 20.

[0601] The solid content was adjusted to 10% using propylene glycol monomethyl ether acetate (PGMEA). The maximum emission wavelength was 521 nm.

[0602] Example 23: Ligand Substitution Reaction 23 (LE-23)

[0603] 5 mL of the quantum dot solution obtained in Synthesis Example 2 was placed in a centrifuge tube, and 20 mL of ethanol was added to precipitate it. The supernatant was removed by centrifugation, and 3 mL of chloroform was added to the precipitate to disperse the quantum dots. Then, 1.0 g of MA-PEG-SH, 1K (MW = 1K, Biochempeg Scientific) represented by the following chemical formula 4-2 was added, and the mixture was heated to 60°C and reacted for one hour under a nitrogen atmosphere.

[0604]

[0605] Next, 25 mL of n-hexane was added to the reaction product to precipitate the quantum dots, and then centrifugation was performed. After the precipitate was separated, propylene glycol monomethyl ether acetate (PGMEA) was added and dispersed so that the solid content became 10%. The maximum emission wavelength was 520 nm.

[0606] Example 24: Ligand Substitution Reaction 24 (LE-24)

[0607] The same procedure as in Example 23 was carried out except that 1.0 g of MA-PEG-SH, 5K (MW=5K, Biochemeg Scientific) represented by the above Chemical Formula 4-2 was used instead of the ligand used in Example 23.

[0608] The solid content was adjusted to 10% using propylene glycol monomethyl ether acetate (PGMEA). The maximum emission wavelength was 521 nm.

[0609] Example 25: Ligand Substitution Reaction 25 (LE-25)

[0610] The same procedure as in Example 23 was carried out except that 1.0 g of MA-PEG-SH, 10K (MW=10K, Biochemeg Scientific) represented by the above Chemical Formula 4-2 was used instead of the ligand used in Example 23.

[0611] The solid content was adjusted to 10% using propylene glycol monomethyl ether acetate (PGMEA). The maximum emission wavelength was 522 nm.

[0612] Example 26: Ligand Substitution Reaction 26 (LE-26)

[0613] The same procedure as in Example 23 was carried out except that ACA-PEG-SH, 1K (MW=1K, Biochempeg Scientific) represented by the following Chemical Formula 4-3 was used instead of the ligand used in Example 23.

[0614]

[0615] The solid content was adjusted to 10% using propylene glycol monomethyl ether acetate (PGMEA). The maximum emission wavelength was 520 nm.

[0616] Example 27: Ligand Substitution Reaction 27 (LE-27)

[0617] The same procedure as in Example 23 was performed except that ACA-PEG-SH,5K (MW=5K, Biochempeg Scientific) represented by the above Chemical Formula 4-3 was used instead of the ligand used in Example 23.

[0618] The solid content was adjusted to 10% using propylene glycol monomethyl ether acetate (PGMEA). The maximum emission wavelength was 521 nm.

[0619] Example 28: Ligand Substitution Reaction 28 (LE-28)

[0620] The same procedure as in Example 23 was carried out except that ACA-PEG-SH, 10K (MW=10K, Biochemeg Scientific) represented by the above Chemical Formula 4-3 was used instead of the ligand used in Example 23.

[0621] The solid content was adjusted to 10% using propylene glycol monomethyl ether acetate (PGMEA). The maximum emission wavelength was 522 nm.

[0622] Comparative Example 1: Preparation of InP / ZnS core-only quantum dots without ligand exchange reaction

[0623] The quantum dots of Synthesis Example 1 with oleic acid bound to the surface were dispersed in chloroform at a concentration of 10%.

[0624] Comparative Example 2: Preparation of InP / ZnSe / ZnS Core-Shell Quantum Dots without Ligand Exchange Reaction

[0625] The quantum dots of Synthesis Example 2 having oleic acid bound to the surface were dispersed in chloroform at a concentration of 10%.

[0626] Comparative Example 3: Ligand Substitution Reaction 29 (LE-29)

[0627] The same procedure as in Example 1 was carried out except that oleyl phosphate (mono- and di-ester mixture) was used instead of the ligand used in Example 1.

[0628] Comparative Example 4: Ligand Substitution Reaction 30 (LE-30)

[0629] The same procedure as in Example 1 was carried out except that the compound of the following Chemical Formula 1-a was used instead of the ligand used in Example 1.

[0630]

[0631] Comparative Example 5: Ligand Substitution Reaction 31 (LE-31)

[0632] The same procedure as in Example 12 was carried out except that 3-(acetyloxy)propanoic acid (Chem Space Co., Ltd.) represented by the following chemical formula 1-b was used instead of the ligand used in Example 1.

[0633]

[0634] The solid content was adjusted to 10% using propylene glycol monomethyl ether acetate (PGMEA). The maximum emission wavelength was 520 nm.

[0635] Comparative Example 6: Ligand Substitution Reaction 32 (LE-32)

[0636] The same procedure as in Example 23 was carried out except that AC-PEG-SH,20K (MW=20K, Biochempeg Scientific) having the same structure as that of the above Chemical Formula 4-1 but with a larger range of n was used instead of the ligand used in Example 23.

[0637] The solid content was adjusted to 10% using propylene glycol monomethyl ether acetate (PGMEA). The maximum emission wavelength was 523 nm.

[0638] Comparative Example 7: Ligand Substitution Reaction 33 (LE-33)

[0639] The same procedure as in Example 23 was carried out except that MA-PEG-SH,20K (MW=20K, Biochempeg Scientific) having the same structure as that of the above Chemical Formula 4-2 but with a larger range of n was used instead of the ligand used in Example 23.

[0640] The solid content was adjusted to 10% using propylene glycol monomethyl ether acetate (PGMEA). The maximum emission wavelength was 523 nm.

[0641] Comparative Example 8: Ligand Substitution Reaction 34 (LE-34)

[0642] The same procedure as in Example 23 was carried out except that ACA-PEG-SH,20K (MW=20K, Biochempeg Scientific) having the same structure as that of the above Chemical Formula 4-3 but with a larger range of n was used instead of the ligand used in Example 23.

[0643] The solid content was adjusted to 10% using propylene glycol monomethyl ether acetate (PGMEA). The maximum emission wavelength was 523 nm.

[0644] Examples 29 to 53 and Comparative Examples 9 to 12: Preparation of Quantum Dot Dispersions

[0645] The quantum dot dispersions of Examples 29 to 53 and Comparative Examples 9 to 12 were prepared by stirring at room temperature for 4 hours, and the quantum dots, monomers and solvents are described in the following Tables 1 to 3 (unit: weight %). The quantum dots used in preparing the quantum dot dispersions of Examples 29 to 53 and Comparative Examples 9 to 12 of the present invention were powdered quantum dots treated by precipitation using hexane as a precipitation solvent.

[0646] [Table 1]

[0647]

[0648] [Table 2]

[0649]

[0650] [Table 3]

[0651]

[0652] -LE-1P: ligand-substituted quantum dot powder of Example 1

[0653] -LE-2P: ligand-substituted quantum dot powder of Example 2

[0654] -LE-8P: ligand-substituted quantum dot powder of Example 8

[0655] -LE-10P: ligand-substituted quantum dot powder of Example 10

[0656] -LE-13P: ligand-substituted quantum dot powder of Example 13

[0657] -LE-14P: ligand-substituted quantum dot powder of Example 14

[0658] -LE-16P: ligand-substituted quantum dot powder of Example 16

[0659] -LE-17P: ligand-substituted quantum dot powder of Example 17

[0660] -LE-20P: ligand-substituted quantum dot powder of Example 20

[0661] -LE-23P: ligand-substituted quantum dot powder of Example 23

[0662] -LE-26P: ligand-substituted quantum dot powder of Example 26

[0663] -Comparative Example 1P: Quantum dot powder of Comparative Example 1

[0664] -LE-30P: ligand-substituted quantum dot powder of Comparative Example 4

[0665] -M-1: BDDA (1,4-Butanediol diacrylate)

[0666] -M-2: HDDA (1,6-Hexanediol diacrylate)

[0667] -M-3: PETA (Pentaerithritol triacrylate)

[0668] -C-1: Propylene glycol monomethyl ether acetate

[0669] -C-2: n-Pentyl acetate

[0670] -C-3: 3-Methoxy butyl acetate

[0671] -C-4: Propylene glycol monomethyl ether

[0672] Examples 54 to 69 and Comparative Examples 13 to 16: Preparation of Quantum Dot Light Conversion Compositions

[0673] The quantum dot light conversion compositions of Examples 54 to 69 and Comparative Examples 13 to 16 were prepared using the components and contents of Tables 4 and 5 below.

[0674] [Table 4]

[0675]

[0676]

[0677] [Table 5]

[0678]

[0679] A-1: Quantum dot dispersion of Example 29

[0680] A-2: Quantum dot dispersion of Example 30

[0681] A-3: Quantum dot dispersion of Example 31

[0682] A-4: Quantum dot dispersion of Example 32

[0683] A-5: Quantum dot dispersion of Example 33

[0684] A-6: Quantum dot dispersion of Example 34

[0685] A-7: Quantum dot dispersion of Example 35

[0686] A-8: Quantum dot dispersion of Example 36

[0687] A-9: Quantum dot dispersion of Example 37

[0688] A-10: Quantum dot dispersion of Example 38

[0689] A-11: Quantum dot dispersion of Example 39

[0690] A-12: Quantum dot dispersion of Comparative Example 9

[0691] A-13: Quantum dot dispersion of Comparative Example 11

[0692] MN-1: ATM-4E (Shin Nakamura Co., Ltd., Ethoxylated pentaerythritol tetraacrylate)

[0693] MN-2: Pentaerythritol triacrylate

[0694] Scattering particles: TiO2 (Huntsman, TR-88, particle size 220nm)

[0695] PI-1: 4,4'-bis(N,N'-dimethylamino)-benzophenone (manufactured by Hodogaya Chemical Co., Ltd.)

[0696] Examples 70 to 83 and Comparative Examples 17 to 18: Preparation of Self-luminous Photosensitive Resin Compositions

[0697] The self-luminous photosensitive resin compositions of Examples 70 to 83 and Comparative Examples 17 to 18 were produced using the components and contents shown in Tables 6 and 7 below.

[0698] [Table 6]

[0699]

[0700] [Table 7]

[0701]

[0702] A-14: Quantum dot dispersion produced in Example 40

[0703] A-15: Quantum dot dispersion produced in Example 42

[0704] A-16: Quantum dot dispersion produced in Example 47

[0705] A-17: Quantum dot dispersion produced in Example 50

[0706] A-18: Quantum dot dispersion produced in Example 51

[0707] A-19: Quantum dot dispersion produced in Example 53

[0708] A-20: Quantum dot dispersion produced in Comparative Example 12

[0709] BP-1: Cardo-based alkali-soluble resin produced in Synthesis Example 3

[0710] BP-2: Cardo-based alkali-soluble resin produced in Synthesis Example 4

[0711] BP-3: Cardo-based alkali-soluble resin produced in Synthesis Example 5

[0712] BP-4: Acrylic alkali-soluble resin produced in Synthesis Example 6

[0713] Photopolymerizable compound: dipentaerythritol hexaacrylate (KAYARAD DPHA; manufactured by Nippon Kayaku Co., Ltd.)

[0714] Scattering particles: TiO2 (Huntsman, TR-88, particle size 220nm)

[0715] PI-1: 4,4'-bis(N,N'-dimethylamino)-benzophenone (manufactured by Hodogaya Chemical Co., Ltd.)

[0716] PI-2: Irgacure OXE01 (manufactured by Ciba Specialty Chemical)

[0717] Solvent: Propylene glycol monomethyl ether acetate

[0718] Experimental example

[0719] (1) Quantum efficiency

[0720] The quantum efficiency (QY%) of the quantum dot dispersions of Examples 1 to 28 and Comparative Examples 1 to 8 at the initial stage of production and the absolute quantum efficiency (QY%) after standing at room temperature for 15 days were measured using QE-2100 (Otsuka Corporation).

[0721] Since the quantum efficiency decreases due to surface oxidation of quantum dots, the oxidation stability can be confirmed by measuring the decrease in quantum efficiency. That is, the oxidation stability can be confirmed by measuring ΔQY%. The above measurement results are shown in Table 8 below.

[0722] (2)Lightfastness

[0723] The quantum efficiency of the quantum dot dispersions of Examples 1 to 28 and Comparative Examples 1 to 8 at the initial stage of production and the absolute quantum efficiency after being placed in a blue LED light source at room temperature for 7 days were measured using QE-2100 (Otsuka Corporation).

[0724] If the surface of the quantum dot is oxidized due to defects that are not protected by the ligand, the quantum efficiency decreases. The reliability is confirmed by measuring the decrease in absolute quantum efficiency. The above measurement results are shown in Table 8 below.

[0725] [Table 8]

[0726]

[0727] As shown in Table 8, it can be confirmed that the quantum dots of Examples 1 to 28 of the present invention containing one or more ligands represented by Chemical Formula 1 to Chemical Formula 4 on the surface are prevented from being oxidized on the surface of the quantum dots, thereby suppressing the decrease in quantum efficiency. On the other hand, it can be confirmed that the quantum efficiency of the quantum dots of Comparative Examples 1 to 8 is greatly reduced.

[0728] Specifically, the quantum dots of Examples 1 to 28 maintain a quantum efficiency of more than about 85% compared to the initial quantum efficiency even after being placed at room temperature for 15 days, and maintain a quantum efficiency of more than about 80% compared to the initial quantum efficiency even after being placed under a blue LED light source at room temperature for 7 days, indicating excellent oxidation stability and light resistance.

[0729] On the other hand, it can be confirmed that the quantum efficiency and light resistance of the quantum dots of Comparative Examples 1 to 8 are reduced. In particular, the quantum efficiency of the quantum dots of Comparative Examples 1 to 2 dropped significantly to below about 50% compared to the initial quantum efficiency after being placed at room temperature for 15 days, and after being placed under a blue LED light source for 7 days, it showed a level of about 40% compared to the initial quantum efficiency, showing a significantly reduced quantum efficiency and light resistance. In addition, in the case of Comparative Examples 3 and 4, it was confirmed that the initial quantum efficiency itself was not high. Furthermore, in the case of Comparative Examples 5 to 8, the quantum efficiency and light resistance were also significantly reduced.

[0730] As described above, it was confirmed that when the quantum dot surface contains one or more compounds represented by Chemical Formulae 1 to 4 as ligands, the surface of the quantum dot is protected, the oxidation stability is excellent, and the quantum efficiency is prevented from decreasing, thereby improving the reliability.

[0731] (3) Viscosity stability evaluation

[0732] For the quantum dot dispersions of Examples 29 to 53 and Comparative Examples 9 to 12, the initial viscosity and the viscosity after storage at a low temperature of 5° C. for 1 month were measured using an R-type viscometer (VISCOMETER MODEL RE120L SYSTEM, manufactured by Toki Sangyo Co., Ltd.) at a rotation speed of 20 rpm and a temperature of 30° C. The viscosity stability was evaluated by the viscosity change rate and is recorded in Table 9.

[0733] <Evaluation Criteria>

[0734] ○: Viscosity change rate is less than 105%

[0735] △: Viscosity change rate is greater than 105% and less than 110%

[0736] ×: Viscosity change rate is greater than 110%

[0737] (4) Dispersion particle size evaluation

[0738] The dispersed particle sizes of the quantum dot dispersions of Examples 29 to 53 and Comparative Examples 9 to 12 were measured using ELSZ-2000ZS (manufactured by Otsuka Corporation), and the results are shown in the following Table 9. When the dispersed particle size is 4 nm to 8.5 nm, excellent dispersion characteristics can be exhibited.

[0739] [Table 9]

[0740] Viscosity stability Dispersed particle size (nm) Embodiment 29 ○ 5.7 Embodiment 30 ○ 6.6 Embodiment 31 ○ 6.1 Embodiment 32 ○ 5.2 Embodiment 33 ○ 6.7 Embodiment 34 ○ 7.1 Embodiment 35 ○ 5.3 Embodiment 36 △ 6.5 Embodiment 37 ○ 6.4 Embodiment 38 ○ 5.6 Embodiment 39 △ 6.2 Embodiment 40 ○ 6.5 Embodiment 41 ○ 6.4 Embodiment 42 ○ 6.0 Embodiment 43 ○ 7.0 Embodiment 44 ○ 7.5 Embodiment 45 ○ 6.7 Embodiment 46 ○ 7.1 Embodiment 47 ○ 8.2 Embodiment 48 ○ 6.8 Embodiment 49 ○ 6.3 Embodiment 50 ○ 5.1 Embodiment 51 ○ 6.0 Embodiment 52 ○ 5.7 Embodiment 53 ○ 5.6 Comparative Example 9 X Unable to determine Comparative Example 10 X 48 Comparative Example 11 △ 32 Comparative Example 12 △ 21

[0741] As shown in Table 9, it can be confirmed that the quantum dot dispersions of Examples 29 to 53 of the present invention have excellent viscosity stability and show good dispersed particle size. On the other hand, it can be confirmed that the quantum dot dispersions of Comparative Examples 9 to 12 have not only significantly lower viscosity stability than the examples of the present application, but also poor dispersed particle size.

[0742] (5) Fabrication of light conversion coatings and determination of light conversion efficiency

[0743] Each quantum dot light conversion composition prepared in Examples 54 to 69 and Comparative Examples 13 to 16 was coated on a 5 cm × 5 cm glass substrate by inkjet method, and then a 1 kW high pressure mercury lamp containing all g, h, and i rays was used as an ultraviolet light source at 1000 mJ / cm 2 After the irradiation, the film was heated in a heating oven at 180° C. for 30 minutes to produce a light conversion coating.

[0744] The manufactured light conversion coating was placed on a blue light source (XLamp XR-E LED, Royal blue 450, Cree), and the light conversion efficiency was measured using a luminance meter (CAS140CT Spectrometer, Instrumentsystems) and the following mathematical formula 1. The results are shown in Table 10.

[0745] The higher the light conversion efficiency (%), the better the brightness can be obtained.

[0746] [Mathematical formula 1]

[0747]

[0748] (6) Number of continuous injections

[0749] After the quantum dot light conversion compositions of the above-mentioned Examples 54 to 68 and Comparative Examples 13 to 16 were filled in the inkjet printing equipment of Unijet, the temperature of the nozzle was fixed at 40°C, and then the inkjet was repeatedly performed for 1 minute and then left for 30 minutes until the nozzle of the nozzle head was clogged and could not be discharged, thereby evaluating the number of continuous injections. The results are shown in Table 10.

[0750] The greater the number of continuous injections, the more excellent characteristics can be obtained in terms of the continuous process.

[0751] (7) Coating hardness

[0752] The degree of cure of the coating film produced in the above Experimental Example (5) was measured at a high temperature of 150° C. using a hardness meter (HM500; manufactured by Fischer) and the surface hardness was evaluated according to the following criteria. The results are shown in Table 10 below.

[0753] <Evaluation Criteria>

[0754] ○: Surface hardness is 50 or more

[0755] △: Surface hardness is 30 or more and less than 50

[0756] ×: Surface hardness less than 30

[0757] [Table 10]

[0758] Photoconversion efficiency (%) Continuous injection times Coating hardness Embodiment 54 38% More than 5 times ○ Embodiment 55 34% More than 5 times △ Embodiment 56 36% More than 5 times ○ Embodiment 57 35% More than 5 times ○ Embodiment 58 34% 5 times ○ Embodiment 59 34% 5 times △ Embodiment 60 34% More than 5 times ○ Embodiment 61 38% More than 5 times ○ Embodiment 62 34% More than 5 times ○ Embodiment 63 37% 5 times △ Embodiment 64 37% 5 times ○ Embodiment 65 35% More than 5 times ○ Embodiment 66 37% More than 5 times ○ Embodiment 67 37% 4 times ○ Embodiment 68 10% More than 5 times ○ Embodiment 69 15% 4 times △ Comparative Example 13 Unable to determine Unable to determine Unable to determine Comparative Example 14 28% 3 times △ Comparative Example 15 Unable to determine Unable to determine Unable to determine Comparative Example 16 26% 3 times △

[0759] As shown in Table 10, it can be confirmed that the quantum dot light conversion compositions of Examples 54 to 69 of the present invention show excellent effects in light conversion efficiency, number of continuous injections, and coating hardness compared with Comparative Examples 13 to 16. However, in the case of Examples 68 and 69, which deviate from the preferred content range of the quantum dot dispersion, it can be seen that the effect is slightly reduced in some evaluations compared with other Examples.

[0760] On the other hand, in the case of using the quantum dot light conversion compositions of Comparative Examples 13 to 16, it was confirmed that not only the light conversion efficiency but also the number of consecutive injections and the coating film hardness showed a significant reduction effect.

[0761] Color filter manufacturing

[0762] Color filters were manufactured using the self-luminous photosensitive resin compositions manufactured in Examples 70 to 83 and Comparative Examples 17 to 18. Specifically, each of the self-luminous photosensitive resin compositions was applied onto a glass substrate by spin coating, and then placed on a hot plate and maintained at 100° C. for 2 minutes to form a thin film.

[0763] Next, a test photomask having a pattern in which the transmittance changes stepwise within a range of 1 to 100% and a line / space pattern of 1 to 50 μm was placed on the film, and ultraviolet rays were irradiated with a distance of 50 μm from the test photomask.

[0764] At this time, the ultraviolet light source used a 1kW high-pressure mercury lamp containing all g, h, and i rays at 100mJ / cm 2 At this time, no special optical filter was used.

[0765] The film irradiated with ultraviolet light was immersed in a KOH aqueous solution developer solution of pH 10.5 for 2 minutes for development. The glass plate covered with the film was washed with distilled water, dried by blowing nitrogen, and heated in a heating oven at 230° C. for 20 minutes to produce a color filter pattern. The film thickness of the self-luminous color pattern produced above was 10.0 μm.

[0766] (8) Color filter development speed, sensitivity, and pattern stability experiments

[0767] The color filters produced from the self-luminous photosensitive resin compositions of Examples 70 to 83 and Comparative Examples 17 to 18 were used as objects, and the development speed, sensitivity, and pattern stability were measured. The evaluation criteria for each experiment are as follows. The measurement results are described in Table 11.

[0768] Development speed (sec): The time required for the non-exposed area to first dissolve in the developer during development (Spray Developer HPMJ method)

[0769] Sensitivity: The degree to which a thin film without peeling is formed on a sensitivity mask fine pattern (1 to 60) (the lower the value, the better the sensitivity)

[0770] Pattern stability: The degree of pattern error after pattern mask exposure at low exposure (20-100mJ)

[0771] <Pattern Stability Evaluation Criteria>

[0772] ○: No error in the pattern

[0773] △: When there are 1 to 2 errors in the pattern

[0774] ×: There are 3 or more errors in the pattern

[0775] (○, △, and × are the results of confirmation using an optical microscope with a 3D surface imaging instrument)

[0776] (9) Micro pattern formation experiment

[0777] In the color filters produced using the self-luminous photosensitive resins of Examples 70 to 83 and Comparative Examples 17 to 18, the size of the pattern obtained by using a line / space pattern mask designed at 100 μm was measured using an OM instrument (ECLIPSE LV100POL, Nikon Corporation).

[0778] If the difference between the design value of the line / space pattern mask and the measured value of the obtained fine pattern is 20 μm or more, it is difficult to realize fine pixels, and if it is a negative value, it means a critical value that causes process failure.

[0779] (10) Photoconversion efficiency evaluation

[0780] The light conversion coating produced in the pattern portion formed in the pattern of 50 mm x 50 mm regular quadrilateral in the color filter having the above-mentioned self-luminous color filter pattern was placed on the top of a blue light source (XLamp XR-E LED, Royal blue 450, Cree), and then the light conversion efficiency was measured using a brightness meter (CAS140CT Spectrometer, Instrument Systems) and the following mathematical formula 1.

[0781] The higher the light conversion efficiency (%), the better the brightness can be obtained.

[0782] [Mathematical formula 1]

[0783]

[0784] The measurement results are shown in Table 11 below.

[0785] [Table 11]

[0786] Photoconversion efficiency (%) Pattern formation Micro pattern Exposure sensitivity Development speed Embodiment 70 36% O 9 12 47 Embodiment 71 34% O 5 11 44 Embodiment 72 35% O 15 11 42 Embodiment 73 34% O 13 10 45 Embodiment 74 35% O 16 14 45 Embodiment 75 34% O 11 17 41 Embodiment 76 35% △ 14 14 35 Embodiment 77 34% △ 12 13 29 Embodiment 78 34% O 13 11 38 Embodiment 79 33% O 11 14 32 Embodiment 80 37% O 9 13 42 Embodiment 81 34% △ 13 10 44 Embodiment 82 35% O 12 14 38 Embodiment 83 12% O 24 8 72 Comparative Example 17 21% X -2 10 33 Comparative Example 18 Unable to determine X Unable to determine Unable to determine Unable to determine

[0787] As shown in Table 11, it can be confirmed that the self-luminous photosensitive resin compositions of Examples 70 to 83 of the present invention are superior in light conversion efficiency, pattern forming properties, fine pattern forming effects, and exposure reduction effects, and are also superior in development speed, compared to Comparative Examples 17 and 18. However, in the case of Example 83, which deviates from the preferred content range of the quantum dot dispersion, it can be seen that the effect is slightly reduced in some evaluations compared to other Examples.

Claims

1. A quantum dot light conversion composition comprising a quantum dot dispersion and one or more selected from scattering particles, a photopolymerizable compound, a photopolymerizable initiator and a solvent, The quantum dot dispersion is prepared by adding quantum dots to one or more of a monomer and a solvent and dispersing them. The quantum dots are quantum dots having a ligand layer on the surface, The ligand layer includes a compound represented by any one of the following chemical formulas 4-1 to 4-3: Chemical formula 4-1 In the chemical formula 4-1, la is an integer in the range of 2K to 10K so that the MW of the compound represented by the chemical formula 4-1 is Chemical formula 4-2 In the chemical formula 4-2, lb is an integer range such that the MW of the compound represented by the chemical formula 4-2 is 1K to 10K. Chemical formula 4-3 In the chemical formula 4-3, lc is an integer range such that the MW of the compound represented by the chemical formula 4-3 is 1K to 10K.

2. According to the quantum dot light conversion composition according to claim 1, the ligand layer further comprises one or more selected from the group consisting of oleic acid, lauric acid, 2-(2-methoxyethoxy)acetic acid, 2-[2-(2-methoxyethoxy)ethoxy]acetic acid and succinic acid mono-[2-(2-methoxy-ethoxy)-ethyl] ester.

3. The quantum dot light conversion composition according to claim 1, wherein the quantum dot has a core-shell structure including a core and a shell covering the core, The core comprises one or more of InP, InZnP, InGaP, CdSe, CdS, CdTe, ZnS, ZnSe, ZnTe, CdSeTe, CdZnS, CdSeS, PbSe, PbS, PbTe, AgInZnS, HgS, HgSe, HgTe, GaN, GaP, GaAs, InGaN, InAs and ZnO, The shell comprises one or more of ZnS, ZnSe, ZnTe, ZnO, CdS, CdSe, CdTe, CdO, InP, InS, GaP, GaN, GaO, InZnP, InGaP, InGaN, InZnSCdSe, PbS, TiO, SrSe and HgSe. 4 . The quantum dot light conversion composition according to claim 1 , wherein the monomer comprises at least one selected from a monofunctional monomer, a difunctional monomer, and a multifunctional monomer.

5. The quantum dot light conversion composition according to claim 1, wherein the solvent comprises one or more selected from alkylene glycol monoalkyl ethers, diethylene glycol dialkyl ethers, methyl cellosolve acetate, ethyl cellosolve acetate, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, propylene glycol monopropyl ether acetate and methoxybutyl acetate. 6 . A self-luminous photosensitive resin composition comprising the quantum dot dispersion according to claim 1 , scattering particles, a photopolymerizable compound, a photopolymerizable initiator, an alkali-soluble resin and a solvent. 7 . The self-luminous photosensitive resin composition according to claim 6 , wherein the alkali-soluble resin comprises at least one of an acrylic alkali-soluble resin and a Cardo alkali-soluble resin.

8. A quantum dot light-emitting diode, comprising the quantum dot light conversion composition according to any one of claims 1 to 5. 9 . A quantum dot film comprising the quantum dot light conversion composition according to claim 1 . 10 . A light conversion laminate substrate, formed using the quantum dot light conversion composition according to claim 1 . 11 . A color filter formed using the self-luminous photosensitive resin composition according to claim 6 . 12 . An image display device comprising the light conversion laminate substrate according to claim 10 . 13 . An image display device comprising the color filter according to claim 11 .

Citation Information

Patent Citations

  • new kind of decorated fabric

    CH20347A

  • Luminescence complex, composition including the complex, hardened member of the composition, optical sheet, backlight unit, and display device

    KR101628065B1

  • Quantum dot-containing composition, wavelength conversion member, backlight unit and liquid crystal display device

    KR1020180002716A

  • Quantum dot ink

    CN106009930A

  • Polymerizable quantum dot and application thereof

    CN106032468A